Silicon-carbon mixture, its preparation method, negative electrode active material and lithium secondary battery containing the same
The use of a silicon-carbon mixture with a controlled oxygen-to-silicon molar ratio in lithium secondary batteries addresses the challenges of volume expansion and cycle degradation, achieving improved capacity retention and efficiency.
Patent Information
- Application Number
- JP2024556477
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2023-03-24
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2043-03-24
AI Technical Summary
Existing silicon-based negative electrode active materials for lithium secondary batteries face challenges such as significant volume expansion (up to 300%) during lithium intercalation, leading to electrode degradation, reduced cycle characteristics, and capacity retention issues.
A silicon-carbon mixture comprising silicon particles, magnesium silicate, and carbon, with a controlled molar ratio of oxygen to silicon atoms within a specific range, is used as a negative electrode active material. This mixture is prepared by obtaining two composite materials and mixing them, with the first composite material containing silicon particles and carbon, and the second composite material containing additional silicon particles, magnesium silicate, and carbon.
The silicon-carbon mixture effectively improves the performance of lithium secondary batteries by maintaining excellent capacity retention even after several thousand cycles, enhancing discharge capacity, initial efficiency, and overall reliability.
Smart Images

Figure 2025510152000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon-carbon mixture, a method for preparing the same, and a negative electrode active material and a lithium secondary battery containing the same. [Background technology]
[0002] In recent years, with the development of the information and communications industry, electronic devices have become smaller, lighter, thinner, and more portable, and this has led to an increased demand for higher energy density batteries to be used as power sources for these devices. Lithium secondary batteries are the battery that best meets this demand, and not only are there active studies on small batteries using these batteries, but they are also being actively applied to large electronic devices such as automobiles and power storage systems.
[0003] Carbon materials are widely used as the negative electrode active material for such lithium secondary batteries. Silicon-based negative electrode active materials are being researched to further improve the capacity of batteries. The theoretical capacity of silicon (4,199 mAh / g) is more than 10 times that of graphite (372 mAh / g), so a significant improvement in battery capacity is expected.
[0004] The reaction scheme when lithium is intercalated into silicon is, for example, as follows: [Reaction Scheme 1] [ka]
[0005] The silicon-based anode active materials according to the above reaction scheme can form high-capacity alloys containing up to 4.4 lithium atoms per silicon atom. However, in most silicon-based anode active materials, the intercalation of lithium causes a volume expansion of up to 300%, which destroys the anode and makes it difficult to achieve high cycleability.
[0006] This volume change may also cause cracks on the surface of the negative electrode active material, forming ionic substances inside the negative electrode active material, which may cause the negative electrode active material to electrically peel off from the current collector. This phenomenon of electrical peeling may significantly reduce the capacity retention rate of the battery.
[0007] To solve this problem, Japanese Patent Publication No. 4393610 discloses a negative electrode active material in which silicon and carbon are mechanically processed to form a composite material, and the surfaces of the silicon particles are coated with a carbon layer using a chemical vapor deposition (CVD) method.
[0008] Furthermore, JP 2016-502253 A discloses a negative electrode active material that contains porous silicon-based particles and carbon particles, in which the carbon particles contain fine carbon particles and coarse carbon particles that have different average particle sizes.
[0009] However, these prior art documents relate to negative electrode active materials containing silicon and carbon, but there is a limit to suppressing volume expansion and contraction during charging and discharging. When cycles are repeated several thousand times for a long period of time, the capacity retention rate drops significantly, and reliability drops. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent No. 4393610 [Patent Document 2] JP 2016-502253 A [Patent Document 3] Korean Patent Application Publication No. 2018-0106485 Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a silicon-carbon mixture which contains two or more composite materials, silicon particles, magnesium silicate and carbon, and in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is controlled within a specific range, thereby improving the performance of lithium secondary batteries when used as a negative electrode active material.
[0012] Another object of the present invention is to provide a method for preparing said silicon-carbon mixture.
[0013] It is still another object of the present invention to provide a negative electrode active material containing the silicon-carbon mixture and a lithium secondary battery containing the same. [Means for solving the problem]
[0014] In order to achieve the above object, one embodiment of the present invention provides a silicon-carbon mixture comprising two or more composite materials, the silicon-carbon mixture comprising silicon particles, magnesium silicate, and carbon, the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) being 0.06 and 0.90.
[0015] Another embodiment provides a method for preparing the silicon-carbon mixture, comprising a first step of obtaining a first composite material; a second step of obtaining a second composite material; and a third step of mixing the first composite material with the second composite material, wherein the first composite material comprises first silicon particles and a first carbon, and the second composite material comprises second silicon particles, magnesium silicate, and a second carbon.
[0016] Yet another embodiment provides an active negative electrode material comprising the silicon-carbon mixture.
[0017] Furthermore, another embodiment provides a lithium secondary battery including the negative electrode active material. Effect of the Invention
[0018] According to the present embodiment, a silicon-carbon mixture is provided that includes two or more composite materials, silicon particles, magnesium silicate, and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is controlled within a specific range. Therefore, a lithium secondary battery with excellent performance and well-balanced discharge capacity, initial efficiency, and capacity retention rate during cycles can be realized.
[0019] In particular, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is controlled within a specific range, making it easy to control the carbon content and porosity. As a result, excellent capacity retention can be maintained even after several thousand cycles over a long period of time, thereby further improving reliability.
[0020] Additionally, the method of one embodiment has the advantage that it allows for mass production via a continuous process with a minimum of steps. [Brief description of the drawings]
[0021] The following drawings attached to this specification show preferred embodiments of the present invention, and are useful for further understanding of the technical concept of the present invention together with the description of the present invention. Therefore, the present invention should not be interpreted as being limited only to those depicted in the drawings.
[0022] [Figure 1] FIG. 1 shows the results of analyzing the crystal structure of the silicon-carbon mixture prepared in Example 1 using an X-ray diffraction analyzer (X'Pert3, manufactured by Malvern Panalytical). [Diagram 2] FIG. 2 shows the results of analyzing the crystal structure of the silicon-carbon mixture prepared in Example 7 using an X-ray diffraction analyzer (X'Pert3, manufactured by Malvern Panalytical). [Diagram 3] FIG. 3 is an ion beam scanning electron microscope (FIB-SEM) photograph of the porous silicon composite material prepared in Preparation Example 2-1 observed at 10,000 times. [Figure 4]FIG. 4 is an ion beam scanning electron microscope (FIB-SEM) photograph of the porous silicon composite material prepared in Preparation Example 2-1 observed at 30,000 times. [Diagram 5] FIG. 5 is an ion beam scanning electron microscope (FIB-SEM) photograph of the porous silicon composite material prepared in Preparation Example 2-1 at 100,000 magnifications. [Figure 6] FIG. 6 is a scanning electron microscope (FE-SEM) photograph of the first composite material prepared in Preparation Example 3-1 observed at 10,000 magnifications. [Figure 7] FIG. 7 is a bright-field image of the first composite material prepared in Preparation Example 3-1, taken with a transmission electron microscope (FE-TEM). [Figure 8] FIG. 8 is a photograph of a dark-field image and a bright-field image of the first composite material prepared in Preparation Example 3-1, taken with a transmission electron microscope (FE-TEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention is not limited to the following disclosure, but can be modified in various forms without departing from the spirit of the invention.
[0024] In this specification, when a component is referred to as "comprising" an element, it should be understood that the component may also include other elements, unless otherwise specified.
[0025] Furthermore, all numbers and expressions relating to quantities of ingredients, reaction conditions, and the like used herein are understood to be modified by the term "about" unless otherwise specified. [Silicon-carbon mixture]
[0026] In one embodiment, the silicon-carbon mixture comprises two or more composite materials, including silicon particles, magnesium silicate, and carbon, with a molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) of 0.06 and 0.90.
[0027] The silicon-carbon mixture according to one embodiment includes two or more composite materials, and contains silicon particles, magnesium silicate, and carbon, in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is controlled within a specific range, thereby realizing a silicon-carbon mixture having desired structure and physical properties. When the silicon-carbon mixture is applied to the negative electrode active material of a lithium secondary battery, the discharge capacity, initial efficiency, and capacity retention rate during cycling can all be improved.
[0028] The molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is preferably 0.09 to 0.80, more preferably 0.09 to 0.60, even more preferably 0.10 to less than 0.60, and most preferably 0.1 to 0.50. A silicon-carbon mixture satisfying the above molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is applied to the negative electrode active material, so that the content of silicon particles as the active material can be increased, thereby simultaneously improving the capacity retention, discharge capacity, and initial efficiency of the lithium secondary battery. In particular, by controlling the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the mixture within a specific range, the structure of the pores and the porosity can be controlled, which is an important advantage in that excellent capacity retention can be maintained even after several thousand or more cycles are repeated for a long period of time, and reliability is improved.
[0029] If the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is smaller than the above range, the production is not easy due to process problems, and if the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture exceeds the above range, the desired effect may be reduced.
[0030] Furthermore, the molar ratio (Mg / Si) of magnesium (Mg) atoms to silicon (Si) atoms in the silicon-carbon mixture may be 0.009 to 0.55, 0.009 to 0.30, or 0.009 to 0.10. When the molar ratio (Mg / Si) of magnesium (Mg) atoms to silicon (Si) atoms in the silicon-carbon mixture satisfies the above range, the resistance when lithium is desorbed and intercalated decreases, and therefore the discharge capacity, initial efficiency, and capacity retention rate after cycling of the lithium secondary battery can be further improved.
[0031] Furthermore, the two or more composite materials can include a first composite material and a second composite material having different compositions, structures, and physical properties.
[0032] Furthermore, according to various embodiments, the content of each component contained in the first composite material and the second composite material and their mixing range can be adjusted to the optimal range required to improve the performance of the lithium secondary battery. In the manufacturing method, the etching conditions and carbon coating conditions can be adjusted in various ways, thereby optimizing the physical properties of the silicon-carbon mixture, such as the specific surface area, density, and porosity. Therefore, the performance and reliability of the lithium secondary battery can be further improved.
[0033] The specific structures, components and contents, and physical properties of the first composite material and the second composite material contained in the silicon-carbon mixture are as follows:
[0034] The weight ratio of the first composite material to the second composite material can be an important factor in achieving the desired performance of the lithium secondary battery.
[0035] For example, the weight ratio of the first composite material to the second composite material may be 90:10 to 5:95, 90:10 to 10:90, 90:10 to 20:80, 90:10 to 50:50, 90:10 to 60:40, 90:10 to 65:35, or 90:10 to 70:30. When the weight ratio of the first composite material to the second composite material satisfies the above range, the desired effect may be easily achieved, and in particular, a lithium secondary battery having excellent performance with a well-balanced discharge capacity, initial efficiency, and capacity retention rate during cycling can be provided.
[0036] Furthermore, since the silicon-carbon mixture of one embodiment contains the first composite material and the second composite material uniformly mixed within the above ranges, by adjusting the physical properties of the final silicon-carbon mixture, such as the silicon particle size, porosity, magnesium content, specific surface area, thermal expansion coefficient, and porosity, it is possible to realize a lithium secondary battery having the desired characteristics for its application.
[0037] In the weight ratio of the first composite material to the second composite material, if the weight ratio of the first composite material to the second composite material is outside the above range, and the content of the first composite material is too low or the content of the second composite material is too high, it becomes difficult to achieve the desired molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture, and the effect of mitigating the volume expansion of silicon particles due to charging and discharging may decrease. In such a case, the cycle characteristics and discharge capacity of the lithium secondary battery may decrease. In addition, the capacity retention rate after cycling of the lithium secondary battery made of the silicon-carbon mixture may decrease.
[0038] On the other hand, the silicon-carbon mixture includes magnesium silicate. Furthermore, the silicon-carbon mixture can include magnesium silicate contained in a second composite material described below.
[0039] Furthermore, the carbon contained in the silicon-carbon mixture can include a first carbon and a second carbon, which will be described later.
[0040] On the other hand, the content of magnesium (Mg) in the silicon-carbon mixture is 0.1% by weight to 15% by weight, preferably 0.1% by weight to 10% by weight, more preferably 0.5% by weight to 5% by weight, based on the total weight of the silicon-carbon mixture. If the content of magnesium (Mg) in the silicon-carbon mixture is equal to or greater than the lower limit of the above range, the initial efficiency of the lithium secondary battery can be improved. If the content is equal to or less than the upper limit of the range, this may be advantageous in terms of the charge / discharge capacity, cycle characteristics, and handling stability of the lithium secondary battery.
[0041] The oxygen (O) content in the silicon-carbon mixture may be from 1 wt% to 25 wt%, preferably from 1 wt% to 21 wt%, more preferably from 1 wt% to 17 wt%, and even more preferably from 3 wt% to 17 wt%, based on the total weight of the silicon-carbon mixture.
[0042] If the content of oxygen (O) in the silicon-carbon mixture is less than the above range, the degree of expansion during charging of the lithium secondary battery increases, and the cycle characteristics deteriorate. Also, if the content of oxygen (O) in the silicon-carbon mixture exceeds the above range, when the silicon-carbon mixture is used as the negative electrode active material, there is a concern that the irreversible reaction with lithium increases, the initial charge-discharge efficiency decreases, and the silicon-carbon mixture is easily peeled off from the negative electrode current collector, resulting in a deterioration in the charge-discharge cycle of the lithium secondary battery.
[0043] The silicon (Si) content in the silicon-carbon mixture may be 35% by weight to 80% by weight, preferably 40% by weight to 80% by weight, more preferably 45% by weight to 80% by weight, and even more preferably 45% by weight to 70% by weight, based on the total weight of the silicon-carbon mixture.
[0044] If the silicon (Si) content in the silicon-carbon mixture is less than the above range, the amount of active material for absorbing and releasing lithium is reduced, and the charge-discharge capacity of the lithium secondary battery may decrease. On the other hand, if the content exceeds the above range, the charge-discharge capacity of the lithium secondary battery may increase, but on the other hand, the expansion and contraction of the electrode during charging and discharging may become excessively large, and the negative electrode active material powder may be further pulverized, which may decrease the cycle characteristics of the lithium secondary battery.
[0045] The carbon (C) content in the silicon-carbon mixture may be 9% by weight to 50% by weight, preferably 9% by weight to 40% by weight, and more preferably 10% by weight to 35% by weight, based on the total weight of the silicon-carbon mixture.
[0046] If the carbon (C) content in the silicon-carbon mixture is less than the above range, the effect of improving the electrical conductivity is small, and there is a concern that the electrode life characteristics of the lithium secondary battery may be reduced. Also, if the carbon (C) content in the silicon-carbon mixture exceeds the above range, the discharge capacity of the lithium secondary battery may decrease, and the bulk density may decrease, so that the discharge capacity per unit volume may decrease.
[0047] On the other hand, the silicon-carbon mixture can further contain silicon oxide (also called silicon oxide compound). In this case, the capacity characteristics and life characteristics of the lithium secondary battery can be further improved and the volume expansion can be suppressed. In particular, the silicon oxide can be uniformly distributed with the silicon particles. In such a case, the volume expansion can be reduced.
[0048] The silicon oxide contained in the silicon-carbon mixture can include a first silicon oxide, a second silicon oxide, and combinations thereof as described below.
[0049] Furthermore, silicon oxide is SiO x It may be a compound represented by (0.4≦x≦2).
[0050] That is, the silicon-carbon mixture is silicon oxide (SiO xcan further contain (0.4 < x ≤ 2).
[0051] Specifically, silicon oxide (SiO x (0.4 < x ≤ 2) can be used in an amount of 0.1% by weight to 5% by weight based on the total weight of the silicon-carbon mixture.
[0052] When the content of silicon oxide is outside the above range, silicon oxide may react with lithium to form strong alkali compounds such as Li 4 SiO 4 or Li 2 O. Silicon oxide is preferably amorphous. When silicon oxide is amorphous, volume changes of silicon particles during intercalation and desorption of lithium can be prevented or mitigated, and side reactions between silicon particles and the electrolyte can be prevented or reduced.
[0053] On the other hand, the silicon particles contained in the silicon-carbon mixture can contain first silicon particles and second silicon particles, as described later.
[0054] Furthermore, the silicon-carbon mixture can contain silicon aggregates in which silicon particles are bonded to each other. The silicon aggregates are as follows.
[0055] When the silicon particles (for example, first silicon particles and second silicon particles) in the silicon-carbon mixture are subjected to X-ray diffraction analysis (converted from the X-ray diffraction analysis results), the average value of the crystallite size of the silicon particles can be 1 nm to 15 nm, preferably 1 nm to 10 nm, more preferably 2 nm to 8 nm, and even more preferably 3 nm to 6 nm. In such cases, the performance of the lithium secondary battery such as discharge capacity, initial efficiency, or cycle life characteristics can be further improved.
[0056] The silicon-carbon mixture can have an average particle size (D 50 ) of 2 μm to 15 μm, preferably 2 μm to 10 μm, more preferably 2 μm to 6 μm.
[0057] In addition, the silicon-carbon mixture has a minimum particle size D of 0.3 or less. min , and maximum particle size D of 8 μm to 30 μm max The silicon-carbon mixture may have a D min and D. max When each of them satisfies the above range, the specific surface area of the silicon-carbon mixture is reduced, thereby making it possible to further improve the initial efficiency and cycle characteristics of the lithium secondary battery.
[0058] On the other hand, the silicon-carbon mixture has a density of 1.8 g / cm 3 ~2.5g / cm 3 , preferably 2.0 g / cm 3 ~2.5g / cm 3 , more preferably 2.0 g / cm 3 ~2.4g / cm 3 If the density of the silicon-carbon mixture is within the above range, it may be more advantageous to achieve the desired effect.
[0059] Silicon-carbon mixture is 2m 2 / g~50m 2 / g, preferably 2m 2 / g~30m 2 / g, more preferably 2m 2 / g~8m 2 / g specific surface area (Brunauer-Emmett-Teller method; BET). If the specific surface area of the silicon-carbon mixture is less than the above range, the charge-discharge characteristics of the lithium secondary battery may be deteriorated. If it exceeds the above range, the contact area between the silicon-carbon mixture and the electrolyte increases, which may promote the decomposition reaction of the electrolyte and cause a side reaction. If the specific surface area of the silicon-carbon mixture satisfies the above range, doping and dedoping of lithium are actively performed, and the irreversible capacity is reduced, thereby achieving excellent capacity characteristics and high rate characteristics.
[0060] The silicon-carbon mixture may contain pores.
[0061] Additionally, the silicon-carbon mixture may contain few pores.
[0062] Additionally, the silicon-carbon mixture may be pore-free.
[0063] When the silicon-carbon mixture contains pores therein, the pores may have the same or different diameters.
[0064] The pores may include internal pores.
[0065] The internal pores include inner pores (also called closed pores) and open pores, which may or may not be connected to other pores, as at least a portion of the pore wall may be open to form an open structure.
[0066] The pores may contain inner pores, which are independent pores that are not connected to other pores because the entire pore wall is closed to form a closed structure.
[0067] The pores may include open pores.
[0068] According to one embodiment, the silicon-carbon mixture has a porosity of 0.1% to 30%, preferably 0.1% to 20%, more preferably 0.1% to 10%. Pores are sometimes used synonymously with voids. Porosity may refer to internal porosity.
[0069] When the porosity of the silicon-carbon mixture satisfies the above range, it is possible to create a buffer effect against volume expansion while maintaining sufficient mechanical strength.
[0070] If the porosity of the silicon-carbon mixture, i.e., the internal porosity of the silicon-carbon mixture, is lower than the above range, it may be difficult to suppress the volume expansion of the negative electrode active material during charging and discharging. If it exceeds the above range, the mechanical strength may decrease due to the presence of many pores in the negative electrode active material, and there is a concern that the negative electrode active material may collapse during the manufacturing process of the lithium secondary battery, for example, during mixing of the negative electrode active material composition (slurry) or during the rolling process after coating.
[0071] If the internal porosity of the silicon-carbon mixture satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it can minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics.
[0072] The internal porosity includes the open pores on the surface and the inner pores of the silicon-carbon mixture.
[0073] As used herein, porosity may be defined as follows in Equation 1: Porosity may also refer to internal porosity.
[0074] [Equation 1] Porosity (%) = Pore volume per unit mass / (Specific volume + Pore volume per unit mass)
[0075] The measurement of the porosity is not particularly limited. According to one embodiment of the present invention, for example, the porosity may be measured using an adsorbed gas such as nitrogen, using a BELSORP (BET device) manufactured by BEL JAPAN Co., Ltd., or may be measured by a mercury permeation method (Hg porosimeter).
[0076] However, in the present invention, it may be difficult to measure accurate values using adsorbed gases such as nitrogen or mercury permeation methods. This may be the case when the surface of each composite material is sealed by the carbon coating of the first composite material and / or the second composite material, and the nitrogen gas does not reach the inner pores. In such a case, the internal porosity can be obtained by adding the value obtained by adsorbed gases such as nitrogen (BET) or mercury permeation method and the internal porosity of the following equation 2.
[0077] [Equation 2] Internal porosity (%) = {1-(measured density / calculated density)} x 100
[0078] Furthermore, in Equation 2, the measured density can be measured using helium.
[0079] In silicon-carbon mixtures, if the inner pores are closed and nitrogen gas and mercury cannot reach the inner pores, the porosity measured by nitrogen adsorption method will be close to the open porosity. Various examples of silicon-carbon mixtures
[0080] The silicon-carbon mixture can have a variety of structures.
[0081] Specifically, the silicon-carbon mixture can include silicon-carbon mixture (1), silicon-carbon mixture (2), and combinations thereof, depending on the porosity.
[0082] Specifically, the silicon-carbon mixture (1) may be a silicon-carbon mixture containing a small amount of pores, and the silicon-carbon mixture (2) may be a porous mixture.
[0083] In one embodiment, the silicon-carbon composite can be formed with controlled porosity by adjusting the carbon coating method and the amount of carbon coating, to obtain silicon-carbon composite (1) and silicon-carbon composite (2). The carbon coating can be formed by chemical pyrolysis deposition (chemical vapor deposition (CVD)).
[0084] Furthermore, the porosity of the silicon-carbon mixture can be controlled by adjusting the etching conditions of the first composite material in the silicon-carbon mixture preparation step described below, such as the etching solution (etchant), its concentration, etching time, etc.; and / or the carbon coating conditions and carbon coating amount of each of the first composite material and the second composite material, such as the type of carbon source, coating temperature, coating time, etc. The technical significance is that this method allows the porosity of the silicon-carbon mixture to be optimized according to the properties required for a lithium secondary battery. Silicon-carbon mixture (1)
[0085] The silicon-carbon mixture (1) in one embodiment may contain a small amount of pores.
[0086] Specifically, the silicon-carbon mixture (1) has an internal porosity of 0.1% to 10%, preferably 0.1% to 8%, and more preferably 0.1% to 5%. The method for measuring the internal porosity is as described above.
[0087] If the internal porosity of the silicon-carbon mixture (1) satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics.
[0088] The internal porosity of the silicon-carbon mixture (1) can be controlled by adjusting the etching conditions, carbon coating conditions, and carbon coating amount of each of the first and second composite materials.
[0089] For example, the internal porosity of the silicon composite material obtained by etching the first composite material before carbon coating (step 1-1 or 1-2 in the preparation process described below) may be 10% to 50%, preferably 15% to 50%, more preferably 20% to 50%. However, the internal porosity of the first composite material obtained by forming the first carbon inside the silicon composite material using a chemical pyrolysis deposition method after etching (step 1-3 in the preparation method described below) and forming the first carbon layer on the surface of the silicon composite material can be adjusted by adjusting the carbon coating conditions and the carbon coating amount so that the silicon-carbon mixture (1) has an internal porosity in the above range.
[0090] That is, in the first composite material preparation method, the large amount of internal pores present in the silicon composite material formed after etching may be filled with carbon by carbon coating by chemical pyrolysis deposition, and the amount of carbon filled in the internal pores can be adjusted by controlling the carbon coating conditions and the carbon coating amount so that the silicon-carbon mixture (1) has an internal porosity that satisfies the above range.
[0091] On the other hand, the silicon-carbon mixture (1) may have an inner porosity of 0.1% to 6%, preferably 0.1% to 5%, and more preferably 0.1% to 4%.
[0092] If the porosity of the silicon-carbon mixture (1) satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics.
[0093] When the internal porosity and / or inner porosity of the silicon-carbon mixture (1) each satisfy the above range, excellent capacity retention can be maintained even after several thousand or more cycles are repeated for a long period of time, resulting in a significant advantage in that reliability is improved. Silicon-carbon mixture (2)
[0094] The silicon-carbon mixture (2) in one embodiment may be porous as it contains a large amount of pores.
[0095] Specifically, the silicon-carbon mixture (2) may have an internal porosity of 4% to 20%, preferably 6% to 20%, and more preferably 8% to 20%.
[0096] When the internal porosity of the silicon-carbon mixture (2) satisfies the above range, the volume expansion of silicon particles that may occur during charging and discharging of a lithium secondary battery can be mitigated and suppressed through the pores.
[0097] If the internal porosity of the silicon-carbon mixture (2) exceeds the above range, the mechanical strength is reduced due to the large number of pores present in the negative electrode active material, and the negative electrode active material may collapse during the production process of the lithium secondary battery, for example, during mixing of the negative electrode active material composition (slurry) or during the rolling process after coating.
[0098] On the other hand, the silicon-carbon mixture (2) has an inner porosity of 2% to 10%, preferably more than 4% to 10%, and more preferably 6% to 10%.
[0099] If the porosity of the silicon-carbon mixture (2) satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics.
[0100] Since the silicon-carbon mixture (2) has a porous structure, the electrolyte can easily permeate into the silicon-carbon mixture (2), thereby improving the charge-discharge characteristics of the lithium secondary battery.
[0101] The first and second composite materials contained in the silicon-carbon mixture are described in detail below. <First composite material>
[0102] In one embodiment of the silicon-carbon mixture, the first composite material includes first silicon particles and first carbon.
[0103] Specifically, the first composite material can include first silicon particles, and further, the first composite material can include first silicon agglomerates in which the first silicon particles are bonded to each other.
[0104] Specifically, the first composite material may include a first silicon aggregate having a three-dimensional (3D) structure in which two or more first silicon particles are bonded to each other. Since the first silicon particles are filled with lithium, if the first composite material does not include the first silicon particles, the capacity of the lithium secondary battery may decrease. In particular, by using the first silicon aggregate in which the first silicon particles are bonded to each other, it is possible to obtain excellent mechanical properties such as strength, prepare a negative electrode active material composition with good dispersibility, and apply the negative electrode active material composition with excellent processability onto a current collector.
[0105] According to one embodiment, the first composite material can include a silicon composite material including first silicon particles and a first carbon.
[0106] Furthermore, the first silicon aggregates can be uniformly distributed inside the first composite material, specifically inside the silicon composite material, and the first silicon particles can include silicon particles that are not bonded to each other. The first silicon particles and / or the first silicon aggregates can be uniformly distributed inside the first composite material, specifically inside the silicon composite material. In this case, excellent electrochemical properties such as charging and discharging can be achieved.
[0107] The first composite material can include first silicon particles, specifically, first silicon aggregates in which the first silicon particles are bonded (or connected) to each other. The first carbon layer can be formed on the surface of the first silicon particles and / or the first silicon aggregates. The first carbon can be formed between the first silicon particles because it is uniformly dispersed and / or distributed. Furthermore, the first carbon layer can be formed on the surface of the silicon composite material.
[0108] For example, the first composite material can include a first carbon layer on a surface of the first silicon particles and / or first silicon agglomerates, and a first carbon layer on a surface of a silicon composite material including the first silicon particles and / or first silicon agglomerates.
[0109] As used herein, "bonded (or interconnected)" refers to a state in which silicon particles in the first composite material are bonded (fused) to at least one other silicon particle and connected to each other, or to a structure in which silicon particles are continuously connected (silicon agglomerates).
[0110] The inside of the first composite material can be more firmly connected by the first carbon and the first carbon layer, which can minimize crushing of the silicon-carbon mixture including the first composite material due to volume change during charging and discharging of the lithium secondary battery.
[0111] The first composite material is a composite material in which first silicon aggregates, in which a plurality of first silicon particles are bonded to each other, are uniformly distributed in a composite material having a single mass-like structure, for example, polyhedral, spherical, etc. It may be a single composite material in which the first carbon and the first carbon-containing first carbon layer surround one or more surfaces of the first silicon particles or a part or all of the surface of the secondary first silicon particles (first silicon aggregates) formed by agglomeration of two or more of the first silicon particles.
[0112] In the first composite material, the inside of the silicon composite material obtained after etching and before carbon coating may have a structure similar to a three-dimensional pomegranate structure (hereinafter referred to as pomegranate structure). In the pomegranate structure, walls may be formed inside the core with the nano-sized first silicon particles bonded to each other. Furthermore, internal pores surrounded by these walls may be formed. The internal pores may be distributed very uniformly inside the silicon composite material. The internal pores may include inner pores and open pores.
[0113] A large amount of the first carbon can then be filled into the pores by the carbon coating.
[0114] That is, the first composite material has a uniform structure in which the first silicon particles are surrounded by a large amount of the first carbon and the first carbon layer containing the first carbon, so that the conductive paths are sufficient to ensure high conductivity, and the amount of carbon-based negative electrode active material added during the manufacture of the negative electrode can be reduced. In addition, the specific surface area of the first composite material is appropriately adjusted to further improve the performance of the lithium secondary battery.
[0115] On the other hand, the first silicon particles include crystalline particles, and the size of the crystallites as determined by X-ray diffraction analysis (converted from the results of X-ray diffraction analysis) can be 1 nm to 15 nm, and preferably 1 nm to 10 nm.
[0116] If the crystallite size of the first silicon particle is less than the above range, it is difficult to form micropores inside the first composite material, and the decrease in the Coulombic efficiency, which represents the ratio of charge capacity to discharge capacity, cannot be suppressed, and the specific surface area becomes too large, making it impossible to prevent the problem of oxidation when handled in air. Also, if the crystallite size exceeds the above range, the micropores cannot sufficiently suppress the volume expansion of the silicon particles that may occur during charging and discharging, and the decrease in the Coulombic efficiency, which represents the ratio of charge capacity to discharge capacity, due to repeated charging and discharging cannot be suppressed.
[0117] Specifically, when the first composite material of one embodiment is subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target, and calculated using the Scherrer equation based on the full width at half maximum (FWHM) of the Si(220) diffraction peak near 2θ=47.5°, the first silicon particles preferably have a crystallite size of 1 nm to 7.5 nm, more preferably 1 nm to 6 nm.
[0118] As the crystallite size of the first silicon particle is made smaller within the above range, a denser composite material can be obtained, and the strength of the matrix can be improved.Therefore, in this case, the performance of the discharge capacity, initial efficiency, cycle life characteristics, etc. of the lithium secondary battery can be further improved.
[0119] In addition, the first composite material can further include amorphous silicon or silicon in a phase similar thereto. The first silicon particles have high initial efficiency and battery capacity, but undergo very complex crystal changes as they electrochemically absorb, store, and release lithium atoms.
[0120] Meanwhile, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the first composite material may be 0.005 to 0.50, preferably 0.01 to 0.40, more preferably 0.01 to 0.30. The first composite material has a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms that satisfies the above range, and therefore may be more advantageous for satisfying the desired molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture. When applied to a lithium secondary battery, it can improve the discharge capacity and initial efficiency along with excellent capacity retention.
[0121] In the first composite material, the first carbon may be present on the surface of the first silicon particle. Further, the first carbon may be present on the surface and / or inside of the first silicon aggregate contained in the first composite material.
[0122] Additionally, the first carbon may function as a matrix, and the first silicon particles and / or the first silicon agglomerates may be dispersed in the first carbon matrix with pores.
[0123] Specifically, the first composite material may have a sea-island structure in which the first silicon particles or closed pores (v) form islands and the first carbon forms a sea. The pores include open pores and closed pores. The closed pores may include pores whose insides are not covered with the first carbon.
[0124] In the first composite material, the first carbon may be present on the surface or within the open pores of the silicon composite particles that include the first silicon particles.
[0125] The state in which the first silicon particles or the first carbon are uniformly dispersed is confirmed by image observation of a dark-field image or a bright-field image using a transmission electron microscope (TEM).
[0126] Further, the first carbon is present on the surface of the first silicon particles or the first silicon aggregates. The first carbon can function as a matrix, and the first silicon particles and pores can be dispersed in the first carbon matrix.
[0127] Furthermore, the first composite material includes a silicon composite material and a first carbon layer on its surface. The first silicon particles may be present in the silicon composite material, and the first carbon may be included in at least a part of the first carbon layer and inside the silicon composite material.
[0128] Furthermore, according to one embodiment, since the thickness or carbon amount of the first carbon layer can be controlled, not only can a decrease in life characteristics be prevented, but also an appropriate conductivity can be realized, thereby realizing a high-capacity negative electrode active material.
[0129] In addition, the first composite material may further include first silicon oxide (SiOx, 0.1 < x ≦ 2, also referred to as the first silicon oxide compound).
[0130] The first silicon oxide may be formed on the surface of the first silicon particles and / or silicon aggregates.
[0131] Furthermore, the first silicon oxide may be uniformly distributed and present together with the first silicon particles.
[0132] Furthermore, the first silicon oxide may be formed on the surface of the first silicon particles and may be uniformly distributed together with the first silicon particles or the first silicon aggregates.
[0133] The first silicon oxide may be a general term for amorphous silicon oxide (oxygen-containing silicon compound) obtained by cooling and depositing silicon monoxide gas generated by oxidation of metallic silicon, reduction of silicon dioxide, or heating of a mixture of silicon dioxide and metallic silicon.
[0134] For the first silicon oxide SiO x wherein x is 0.4 ≦ x ≦ 2, preferably 0.6 ≦ x ≦ 1.6, more preferably 0.6 ≦ x ≦ 1.2.
[0135] Formula SiO xIn this case, if the value of x is less than the above range, the expansion and contraction during charge and discharge of the lithium secondary battery become large, and the life characteristics may deteriorate. Also, if x exceeds the above range, there may be a problem that the initial efficiency of the lithium secondary battery decreases because the amount of inactive oxide increases.
[0136] Furthermore, the first carbon may be present on the surface of the first silicon oxide (SiO x , 0.1 < x ≤ 2).
[0137] On the other hand, generally, in a negative electrode active material containing silicon, as the ratio of oxygen decreases, the ratio of silicon particles as the active material increases, so the discharge capacity and discharge efficiency improve. However, there may occur a problem that cracks can be formed in the first composite material or the silicon-carbon mixture caused by the volume expansion due to charge and discharge of the silicon particles. As a result, the cycle characteristics of the lithium secondary battery may deteriorate. To solve this problem, silicon dioxide can be contained in the first composite material as an inactive material or an inactive phase.
[0138] Specifically, since silicon dioxide is an inactive material or an inactive phase, it has an effect of relaxing the volume expansion caused by charge and discharge of silicon particles. Silicon dioxide is a component that forms the matrix of the first composite material, and has an effect of increasing the mechanical strength of the matrix of the first composite material to make it more robust and suppressing the generation of cracks even during volume expansion.
[0139] Furthermore, since the content of silicon dioxide is optimized, it is possible to suppress a decrease in the initial capacity and initial efficiency of the lithium secondary battery and improve the cycle characteristics by increasing the strength of the matrix.
[0140] Specifically, according to one embodiment, the first composite material may contain silicon dioxide in an amount of 0.3% by weight to 6% by weight, preferably 0.5% by weight to 6% by weight, more preferably 0.5% by weight to 5% by weight, even more preferably 1% by weight to 4% by weight, and most preferably 1% by weight to 3% by weight, based on the total weight of the first composite material. If the content of silicon dioxide is less than the above range, the effect of improving the cycle characteristics of the lithium secondary battery may be insufficient. If the content exceeds the above range, it becomes difficult to set the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the first composite material to a desired value, and the cycle characteristics and discharge capacity of the lithium secondary battery may be reduced.
[0141] The content of oxygen (O) in the first composite material is 0.1% by weight to 16% by weight, preferably 0.1% by weight to 12% by weight, more preferably 0.1% by weight to 8% by weight, and most preferably 0.1% by weight to 6% by weight, based on the total weight of the first composite material.
[0142] If the content of oxygen (O) in the first composite material is less than the above range, the degree of expansion during charging of the lithium secondary battery increases, and the cycle characteristics deteriorate. If the content of oxygen (O) in the first composite material exceeds the above range, there is a concern that irreversible reactions with lithium increase, the initial charge / discharge efficiency decreases, and the material may easily peel off from the negative electrode current collector, resulting in a deterioration in the charge / discharge cycle of the lithium secondary battery.
[0143] On the other hand, in the first composite material, the content of silicon (Si) may be 35% by weight to 80% by weight, preferably 40% by weight to 80% by weight, more preferably 50% by weight to 80% by weight, based on the total weight of the first composite material. If the content of silicon (Si) in the first composite material is less than the above range, the amount of active material for absorbing and releasing lithium is reduced, and the charge and discharge capacity of the lithium secondary battery may decrease. On the other hand, if the content exceeds the above range, the charge and discharge capacity of the lithium secondary battery may increase, but the expansion and contraction of the electrode during charging and discharging may become excessively large, and the negative electrode active material powder may be further pulverized, resulting in a decrease in cycle characteristics.
[0144] Furthermore, the first composite material includes a silicon composite material and a first carbon layer provided on the surface thereof. The first silicon particles may be present in the silicon composite material, and the first carbon may be contained within the first carbon layer and the silicon composite material.
[0145] The carbon (C) content in the first composite material may be 10% by weight to 50% by weight based on the total weight of the first composite material. Specifically, the carbon (C) content may be 15% by weight to 45% by weight, or 15% by weight to 40% by weight based on the total weight of the first composite material.
[0146] If the content of carbon (C) in the first composite material is less than the above range, the effect of improving the electrical conductivity cannot be expected sufficiently, and the electrode life of the lithium secondary battery may be shortened. If the content of carbon (C) in the first composite material is more than the above range, the discharge capacity of the lithium secondary battery may be reduced, and the charge / discharge capacity per unit volume may be reduced.
[0147] Furthermore, carbon (C) can be contained inside the silicon composite material. The content of carbon (C) contained inside the silicon composite material may be 10% by weight to 45% by weight, preferably 10% by weight to 40% by weight, more preferably 15% by weight to 38% by weight, based on the total weight of the first composite material. When carbon is contained in the silicon composite material within the above content range, sufficient electrical conductivity can be obtained.
[0148] Furthermore, the carbon (C) content in the first composite material, particularly the carbon (C) content in the silicon composite material, may be affected by the porosity.
[0149] For example, the first composite material can include first composite material (1), first composite material (2), or a mixture thereof, depending on the porosity.
[0150] The first composite material (1) may contain a small amount of pores and the first composite material (2) may contain a large amount of pores.
[0151] Specifically, in a first composite material (1) containing a small amount of pores, the carbon (C) content in the silicon composite material can be increased to 30% to 45% by weight based on the total weight of the first composite material. Also, in a porous first composite material (2) containing a large amount of pores, the carbon (C) content in the silicon composite material can be reduced to less than 10% to 30% by weight based on the total weight of the first composite material.
[0152] In this way, the carbon (C) content is adjusted to an optimal range, so that the porosity of the first composite material can be controlled, and therefore, a silicon-carbon mixture with a controlled porosity can be obtained.
[0153] Furthermore, by controlling the porosity of the first composite material, the carbon (C) content in the first composite material can be adjusted to an optimum range.
[0154] The first carbon layer may have a thickness of 2 nm to 100 nm, preferably 10 nm to 80 nm, more preferably 10 nm to 60 nm, and even more preferably 10 nm to 40 nm.
[0155] When the thickness of the first carbon layer is equal to or greater than the lower limit, the electrical conductivity can be improved, whereas when the thickness is equal to or less than the upper limit, the capacity of the lithium secondary battery can be prevented from decreasing.
[0156] The average thickness of the first carbon layer can be measured, for example, by the following procedure.
[0157] First, the composite material, mixture, or negative electrode active material is observed at any magnification using a transmission electron microscope (TEM). The magnification is preferably such that it can be confirmed with the naked eye. Next, the thickness of the carbon layer is measured at any 15 points. In such a case, it is desirable to select the measurement positions as widely and randomly as possible, without concentrating them in a specific area. Finally, the average value of the thickness of the carbon layer at the 15 points is calculated.
[0158] The first carbon layer may include at least one selected from the group consisting of amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers. Specifically, it may include graphene. At least one selected from the group consisting of amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers may be included not only in the first carbon layer present on the surface of the silicon composite material, but also in the interior of the silicon composite material, the surface of the first silicon particle, and the first carbon matrix.
[0159] When the first carbon layer contains amorphous carbon, the strength of the first carbon layer is appropriately maintained, and therefore expansion of the composite material can be suppressed.
[0160] The amorphous carbon may include at least one selected from the group consisting of soft carbon (low-temperature calcined carbon), hard carbon, pitch carbide, mesophase pitch carbide, and calcined coke.
[0161] The raw material of the pitch may be, for example, petroleum-based, coal-based, or a mixture thereof. For example, it may be coal tar pitch, petroleum pitch, organic synthetic pitch obtained by polycondensation of condensed polycyclic aromatic hydrocarbon compounds, or organic synthetic pitch obtained by polycondensation of heteroatom-containing condensed polycyclic aromatic hydrocarbon compounds. Specifically, the raw material of the pitch may be coal tar pitch.
[0162] When the first carbon layer is formed using pitch, the electrical conductivity of the negative electrode active material can be improved through a simple heat treatment process in which the pitch raw material is heat-treated and carbonized.
[0163] In addition, when the first carbon layer contains crystalline carbon, the electrical conductivity of the negative electrode active material can be improved. The crystalline carbon may be at least one selected from the group consisting of plate-shaped, spherical, and fibrous natural graphite and fibrous artificial graphite.
[0164] Also, a first carbon of the same type as the first carbon layer can be formed inside the silicon composite material.
[0165] Meanwhile, the first carbon layer of the first composite material can include one or more carbon layers, or two or more carbon layers.
[0166] For example, the first carbon layer may have a single-layer structure or a multi-layer structure of two or more layers. When the first carbon layer is formed of two or more carbon layers, even if a crack forms on the surface of one of the carbon layers, the carbon layers can maintain an electrically connected state until the other carbon layers without cracks are completely peeled off.
[0167] Specifically, when the first carbon layer of the first composite material includes two or more layers, it can include a 1-1 carbon layer and a 1-2 carbon layer.
[0168] The types of the 1-1 carbon layer and the 1-2 carbon layer are as described above. Here, the types of the 1-1 carbon layer and the 1-2 carbon layer may be different from each other.
[0169] For example, the 1-1 carbon layer can include at least one selected from the group consisting of amorphous carbon, crystalline carbon, graphene, carbon nanotubes, and carbon nanofibers. The 1-2 carbon layer can include reduced graphene oxide (RGO). Reduced graphene oxide can be formed by partially or substantially completely reducing graphene oxide.
[0170] The first silicon composite material has an average particle size (D 50 ) and the average particle size (D 50 ) is the average diameter (D 50 ), that is, the average particle size (D 50 ), that is, the particle size or median size when the cumulative volume is 50%.50 If D is less than the above range, there is a concern that when the negative electrode active material composition (slurry) is prepared using the first composite material, the particles of the first composite material may aggregate and the dispersibility may decrease. 50 If the specific surface area exceeds the above range, the composite particles will expand significantly due to charging of lithium ions, and the binding ability between the composite particles and between the composite particles and the current collector will decrease as charging and discharging are repeated, which may significantly reduce the life characteristics. In addition, there is a concern that the activity may decrease due to a decrease in the specific surface area.
[0171] Meanwhile, the specific surface area of the first composite material can be greatly changed since the surface of the silicon composite particles or the interior of the silicon composite and the pores therein can be covered with a carbon coating.
[0172] The first composite material is 2m 2 / g~50m 2 / g, preferably 2m 2 / g~40m 2 / g, more preferably 2m 2 / g~20m 2 The first composite material may have a specific surface area (Brunauer-Emmett-Teller method; BET) of 100 / g. If the specific surface area of the first composite material is less than the above range, the charge / discharge characteristics of the lithium secondary battery may be deteriorated. If the specific surface area of the first composite material is more than the above range, it may be difficult to prepare a negative electrode active material composition (slurry) suitable for application to the negative electrode current collector of the lithium secondary battery, and the contact area with the electrolyte may increase, accelerating the decomposition reaction of the electrolyte or causing a side reaction in the lithium secondary battery.
[0173] The first composite material had a density of 1.8 g / cm 3 ~2.5g / cm 3 , preferably 2.0 g / cm 3 ~2.5g / cm 3 , more preferably 2.0 g / cm 3 ~2.4g / cm 3 , and even more preferably 2.0 g / cm 3 ~2.35g / cm 3The density can be changed depending on the amount of coverage of the first carbon layer. The amount of carbon is constant, but the greater the density within the above range, the fewer the pores in the first composite material. Therefore, when a silicon-carbon mixture containing the first composite material is used as a negative electrode active material, the electrical conductivity is improved and the strength of the matrix is strengthened, thereby improving the initial efficiency and cycle life characteristics. In this case, the density may refer to the true density. The measurement method is as described above.
[0174] If the density of the first composite material is within the above range, the volume expansion of the negative electrode active material during charging and discharging can be reduced, thereby minimizing cracks in the negative electrode active material, which can prevent deterioration of cycle characteristics and improve the impregnation of the electrolyte, thereby further improving the initial charge and discharge capacity of the lithium secondary battery.
[0175] On the other hand, the first composite material may include pores.
[0176] In the first composite material, the first composite material (1) and the first composite material (2) having different porosities can be obtained by adjusting the carbon coating method and the carbon coating amount. The carbon coating can be formed by a chemical vapor deposition (CVD) method.
[0177] Specifically, in the method for preparing the first composite material described below, the porosity of the first composite materials (1) and (2) can be controlled by adjusting the etching conditions, for example, the etching solution (etchant), its concentration, etching time, etc.; and / or the carbon coating conditions, the amount of carbon coating, for example, the type of carbon source, coating temperature, coating time, etc. First Composite Material (1)
[0178] The first composite material (1) in one embodiment may contain a small amount of pores.
[0179] The definition and measurement method of the pores are as described above.
[0180] Specifically, the first composite material (1) may have an internal porosity of 0.1% to 10%, preferably 0.1% to 8%, and more preferably 0.1% to 5%. The method for measuring the internal porosity is as described above.
[0181] When the internal porosity of the first composite material (1) satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics.
[0182] If the internal porosity of the first composite material (1) is less than the above range, it may become difficult to suppress the volume expansion of the negative electrode active material during charge and discharge.
[0183] On the other hand, the first composite material (1) may have an inner porosity of 0.1% to 8%, preferably 0.1% to 5%, and more preferably 0.1% to 4%.
[0184] If the porosity of the first composite material (1) satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics.
[0185] When the internal porosity and / or the inner porosity of the first composite material (1) each satisfy the above range, excellent capacity retention can be maintained even after several thousand or more cycles are repeated for a long period of time, resulting in a significant advantage in that reliability is improved. First Composite Material (2)
[0186] The first composite material (2) in one embodiment may be porous, as it contains a large amount of pores.
[0187] Specifically, the first composite material (2) may have an internal porosity of more than 10% and not more than 40%, preferably more than 10% and not more than 30%, and more preferably more than 10% and not more than 25%.
[0188] When the internal porosity of the first composite material (2) satisfies the above range, the volume expansion of the silicon particles that may occur during charging and discharging of a lithium secondary battery can be mitigated and suppressed through the pores.
[0189] If the internal porosity of the first composite material (2) exceeds the above range, a large number of pores will be present in the negative electrode active material, and the mechanical strength will decrease, so that the negative electrode active material may collapse during the production process of the lithium secondary battery, for example, during mixing of the negative electrode active material composition (slurry) or during the rolling process after coating.
[0190] Since the first composite material (2) has a porous structure, the electrolyte can easily permeate into the first composite material (2), thereby improving the charge / discharge characteristics of the lithium secondary battery.
[0191] On the other hand, the first composite material (2) may have an inner porosity of 5% to 35% or less, preferably more than 5% to 25% or less, and more preferably more than 5% to 20% or less.
[0192] If the porosity of the first composite material (2) satisfies the above range, when it is applied to the negative electrode active material of a lithium secondary battery, it can obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles, achieve high capacity, and improve life characteristics. <Second composite material>
[0193] In one embodiment of the silicon-carbon mixture, the second composite material can include second silicon particles, magnesium silicate, and second carbon.
[0194] According to one embodiment, the first composite material and the second composite material are used, so that the excellent characteristics of the second composite material, that is, the capacity characteristics (initial capacity) and initial efficiency, can be further improved while solving the problem of the deterioration of the life characteristics of the second composite material. In particular, since the silicon-carbon mixture contains the second composite material, the initial efficiency improving effect of magnesium silicate can be maximized, and thus the performance of the lithium secondary battery can be improved.
[0195] Specifically, the second composite material may include a silicon composite oxide and a second carbon layer on its surface, the second silicon particles and magnesium silicate may be present in the silicon composite oxide, and the second carbon may be included in at least one selected from the group consisting of the second carbon layer, the surface of the second silicon particles, and the surface of the second magnesium silicate.
[0196] Furthermore, the second silicon particles and magnesium silicate can be uniformly distributed inside the silicon composite oxide, which can exhibit excellent electrochemical properties.
[0197] The second silicon particles can include crystalline particles, amorphous particles, or particles having phases similar thereto, or a combination thereof.
[0198] Specifically, the second silicon particles include crystalline particles, and the size of the crystallites in X-ray diffraction analysis can be 3 nm to 15 nm (calculated from the results of X-ray diffraction analysis).
[0199] For example, when the second composite material is subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target and calculated using the Scherrer equation based on the full width at half maximum (FWHM) of the Si(220) diffraction peak at around 2θ=47.5°, the second silicon particles preferably have a crystallite size of 4 nm to 15 nm, more preferably 4 nm to 12 nm, even more preferably 4 nm to 10 nm, and most preferably 4 nm to 8 nm.
[0200] In addition, if the crystallite size of the second silicon particles is less than the above range, the initial efficiency, discharge capacity, and capacity retention rate may be rapidly reduced. If the crystallite size of the second silicon particles satisfies the above range, the Coulomb efficiency, which represents the ratio of charge capacity to discharge capacity, that is, the charge / discharge efficiency, can be improved.
[0201] The second silicon particles may be amorphous particles, crystalline particles with a crystallite size of 4 nm to 15 nm, or a mixture thereof.
[0202] Although it may be advantageous that the second silicon particles are almost 100% amorphous particles, it is difficult to obtain completely amorphous second silicon particles in the process.Therefore, the second silicon particles may be present in a mixed form of amorphous particles and crystalline particles.
[0203] Furthermore, when the second silicon particles are in a mixed form of amorphous particles and crystalline particles, the ratio of amorphous particles may be 50% or more.
[0204] When the second silicon particles contain amorphous particles, crystalline particles with a crystallite size in the above range, or a mixture thereof, cracks during the initial charge and discharge of the lithium secondary battery can be suppressed.
[0205] If some cracks form during the initial charge / discharge of a lithium secondary battery, these cracks may gradually widen during repeated charge / discharge cycles, causing problems in the performance of the lithium secondary battery.
[0206] If the second silicon particles include crystalline particles and the crystallite size of the second silicon particles is less than the above range, the charge / discharge capacity of the lithium secondary battery may decrease, and the reactivity may increase during storage, causing changes in the properties of the material, which may cause problems in the process.
[0207] When the second silicon particles contain crystalline particles and the crystallite size of the second silicon particles is equal to or larger than the lower limit, the lithium secondary battery can maintain excellent charge / discharge characteristics.When the crystallite size of the second silicon particles is equal to or smaller than the upper limit, the lithium secondary battery can be prevented from decreasing in Coulomb efficiency, which represents the ratio of charge capacity to discharge capacity.
[0208] In addition, by further pulverizing the second silicon particles to make them amorphous or to have a crystallite size of 4 nm to 7 nm, the density can be increased, the strength can be strengthened, and the formation of cracks can be prevented, thereby further improving the initial efficiency and cycle life characteristics of the lithium secondary battery.
[0209] The second composite material is a composite material in which the second silicon aggregates, which are formed by bonding a plurality of second silicon particles to each other, are uniformly distributed in the composite material having a single mass structure, for example, a polyhedral, spherical or similar shape. It may be a single composite material in which the second carbon layer containing the second carbon surrounds the surface of one or more second silicon particles, or a part or all of the surface of the secondary second silicon particle (second silicon aggregate) formed by the aggregation of two or more second silicon particles.
[0210] Furthermore, the content of silicon (Si) in the second composite material may be 30 wt% to 60 wt%, 30 wt% to 55 wt%, 35 wt% to 55 wt%, or 35 wt% to 50 wt%, based on the total weight of the second composite material.
[0211] When the content of silicon (Si) in the second composite material satisfies the above range, the charge / discharge capacity and cycle characteristics of the lithium secondary battery can be further improved.
[0212] If the silicon (Si) content is less than the above range, the charge / discharge capacity of the lithium secondary battery may decrease. If the silicon (Si) content exceeds the above range, the charge / discharge capacity of the lithium secondary battery may increase, but on the other hand, the electrode may contract and expand excessively during charging and discharging, which may further pulverize the negative electrode active material powder and decrease the cycle characteristics of the lithium secondary battery.
[0213] On the other hand, according to one embodiment, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the second composite material is 0.8 to 1.2, preferably 0.85 to 1.2, and more preferably 0.9 to 1.2. When the second composite material having a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms that satisfies the above range is used as a negative electrode active material, it is possible to improve the discharge capacity and initial efficiency while maintaining an excellent capacity retention rate.
[0214] According to one embodiment, if the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the second composite material is outside the above range, the capacity characteristics of the secondary battery may be degraded.
[0215] Meanwhile, the second composite material includes magnesium silicate.
[0216] Because the second composite material contains magnesium silicate, it has excellent slurry stability when producing lithium secondary batteries, and can improve the capacity retention, charge / discharge characteristics, and cycle characteristics when applied to lithium secondary batteries.
[0217] Magnesium silicate hardly reacts with lithium ions during charging and discharging of a lithium secondary battery, so it can reduce the expansion and contraction of the electrode when lithium ions are absorbed in the electrode, thereby improving the cycle characteristics of the lithium secondary battery. In addition, the strength of the matrix, which is the continuous phase surrounding silicon, can be strengthened by magnesium silicate.
[0218] Magnesium silicate is represented by the following formula A: [Formula A] [ka]
[0219] In formula A, x is in the range of 0.5≦x≦2, and y is in the range of 2.5≦y≦4.
[0220] Magnesium silicate is MgSiO 3 , Mg 2 SiO 4 , or mixtures thereof.
[0221] Specifically, magnesium silicate is MgSiO 3 Crystal (enstatite) and Mg 2 SiO 4 The crystals may include at least one selected from the group consisting of forsterite and arsenic.
[0222] Additionally, according to one embodiment, the magnesium silicate is MgSiO 3 It may contain Mg crystals. 2 SiO 4 It may contain crystals.
[0223] Magnesium silicate is MgSiO 3 Crystals and Mg 2 SiO 4 If it contains a mixture of crystals, MgSiO 3 Crystals and Mg 2 SiO 4 The crystallinity may vary depending on the amount of magnesium used in the raw material process.
[0224] In addition, magnesium silicate is added in substantial amounts of MgSiO to improve coulombic efficiency, charge / discharge capacity, initial efficiency, and capacity retention. 3 It may contain crystals.
[0225] In this specification, the expression "containing a substantially large amount of" a certain component may mean containing that component as a main component, or may mean containing that component mainly.
[0226] Specifically, according to one embodiment, the magnesium silicate is MgSiO 3 Contains crystals and Mg 2 SiO 4 In such cases, Mg crystals appear in the range of 2θ=22.3° to 23.3° in X-ray diffraction analysis. 2 SiO 4 The intensities (IF) of the X-ray diffraction peaks corresponding to the crystals and the MgSiO 3 The ratio to the intensity (IE) of the X-ray diffraction peak corresponding to the crystal may be greater than 0 and equal to or less than 1, specifically, 0.1 to 1.
[0227] Magnesium silicate (MgSiO) 3 By using a substantially larger amount of crystals, the effect of improving cycle performance during charging and discharging can be enhanced.
[0228] Magnesium silicate is MgSiO 3 Crystals and Mg 2 SiO 4 When Mg crystals are included, the initial efficiency can be improved. 2 SiO 4 The crystals were prepared as MgSiO 3 If more than the crystals are used, the degree of alloying between silicon and lithium atoms decreases, which may result in a decrease in initial discharge characteristics.
[0229] According to one embodiment, the second composite material is MgSiO 3 Crystals and Mg 2 SiO 4 When crystals are included together, the initial efficiency can be further improved.
[0230] The second composite material is MgSiO 3 If it contains crystals, MgSiO 3 Crystals (e.g., with a density of 2.7 g / cm 3 ) is Mg 2 SiO 4 Crystals (e.g., with a density of 3.2 g / cm 3), compared to silicon (for example, density is 2.33 g / cm 3 The volume change due to the volume change of MgSiO is small. Therefore, the cycle characteristics of the lithium secondary battery can be further improved. 3 Crystal and Mg 2 SiO 4 The crystals may act as a diluent or inactive material in the negative electrode active material. 3 When crystals are formed, crushing caused by the shrinkage and expansion of silicon is suppressed, thereby improving initial efficiency.
[0231] In addition, magnesium silicate hardly reacts with lithium ions, so when it is contained in an electrode, it reduces the expansion and contraction of the electrode when lithium ions are absorbed into the electrode, and improves the cycle characteristics of the lithium secondary battery.
[0232] Furthermore, the strength of the matrix, which is the continuous phase surrounding the silicon, can be increased by magnesium silicate.
[0233] Because the second composite material contains magnesium silicate, it is possible to suppress the chemical reaction between the negative electrode active material and the binder during the production of a lithium secondary battery, improve the stability of the slurry, and improve both the stability and cycle characteristics of the negative electrode.
[0234] Magnesium silicate is also known as MgSiO 3 Crystals and Mg 2 SiO 4 When both crystals are included, MgSiO 3 Crystals and Mg 2 SiO 4 It is preferred that the crystals are uniformly distributed, and that the crystallite size is less than 10 nm.
[0235] MgSiO 3 Crystals and Mg 2 SiO 4 If the crystals are uniformly distributed, the second silicon particles as well as MgSiO 3Crystal and Mg 2 SiO 4 The constituent elements of the crystal are diffused into each other, and the phase interfaces are in a bonded state, that is, each phase is in a bonded state at the atomic level. Therefore, the volume change when lithium ions are absorbed and released may be small, and cracks may not easily form in the negative electrode active material even when it is repeatedly charged and discharged. Therefore, there will be almost no decrease in capacity even with a large number of cycles.
[0236] On the other hand, the magnesium (Mg) content in the second composite material may be 2 wt% to 20 wt%, preferably 4 wt% to 15 wt%, and most preferably 4 wt% to 12 wt%, based on the total weight of the second composite material.
[0237] When the content of magnesium (Mg) in the second composite material is equal to or greater than the lower limit of the above range, the initial efficiency of the lithium secondary battery can be improved. When the content of magnesium (Mg) is equal to or less than the upper limit of the above range, it may be advantageous in terms of improving the charge / discharge capacity, cycle characteristics, and handling stability.
[0238] In addition, as the magnesium (Mg) content increases, 2 SiO 4 The content of crystals may increase. As a result, the size of the magnesium silicate crystallites increases, the initial efficiency increases excessively, and the cycle characteristics relatively decrease. Therefore, it may be important to control the magnesium (Mg) content within an optimal range.
[0239] The magnesium silicate may be formed uniformly distributed with the second silicon particles.
[0240] Meanwhile, the second composite material can include a second silicon oxide (also referred to as a second silicon oxide compound).
[0241] The second silicon oxide may include the same or similar compounds as the first silicon oxide.
[0242] Furthermore, the second silicon oxide may be, for example, a silicon-based oxide represented by the formula SiO x (0.5 ≦ x ≦ 1.5). Specifically, the second silicon oxide may be SiOx (0.8 ≦ x ≦ 1.2), and more specifically, SiO x (0.9 < x ≦ 1.1). In the formula SiO x , if the value of x is less than the above range, the expansion and contraction during charge and discharge of the lithium secondary battery may increase, and the life characteristics may deteriorate. Also, if x exceeds the above range, there may be a problem that the initial efficiency of the lithium secondary battery decreases due to an increase in inactive oxides.
[0243] The second silicon oxide can be obtained by a method including mixing and heating silicon powder and silicon dioxide powder, and cooling and depositing the silicon oxide gas generated thereby.
[0244] The second silicon oxide can be used in an amount of 0.1% by weight to 45% by weight, preferably 0.5% by weight to 20% by weight, based on the total weight of the second composite material.
[0245] If the content of the second silicon oxide is less than the above range, the volume expansion characteristics and life characteristics of the lithium secondary battery may deteriorate. If it exceeds the above range, the initial irreversible reaction of the lithium secondary battery may increase.
[0246] According to one embodiment, the silicon composite oxide of the second composite material may include the second silicon oxide, and the second silicon particles, magnesium silicate, and the second silicon oxide may be uniformly mixed and present. Furthermore, the second silicon oxide may be present on the surface of the second silicon particles.
[0247] When the second composite material contains the second silicon particles, the second silicon oxide, and the magnesium silicate, the volume change during the absorption and release of lithium ions is small, and the formation of cracks in the negative electrode active material during repeated charging and discharging can be prevented. In such a case, a rapid decrease in capacity with respect to the number of cycles of the lithium secondary battery can be prevented, and therefore the cycle characteristics of the lithium secondary battery can be improved.
[0248] In addition, the second composite material contains second silicon particles, second silicon oxide, and magnesium silicate, and the second silicon particles are connected and bonded to each other, so that lithium ions are easily released during discharge of the lithium secondary battery. Therefore, the charge and discharge amounts of lithium ions are well balanced, and the initial efficiency (charge and discharge efficiency) can be improved.
[0249] The second silicon oxide may be used in an amount of 40% to 50% by weight based on the total weight of the second composite material.
[0250] If the content of the second silicon oxide is less than the above range, the volume expansion characteristics and life characteristics of the lithium secondary battery may be deteriorated, whereas if the content of the second silicon oxide is more than the above range, the initial irreversible reaction of the lithium secondary battery may be increased.
[0251] The content of oxygen (O) in the second composite material may be 20% by weight to 40% by weight, preferably 25% by weight to 40% by weight, more preferably 25% by weight to 35% by weight, based on the total weight of the second composite material. If the content of oxygen (O) in the second composite material is less than the above range, the degree of expansion during charging of the lithium secondary battery increases, and the cycle characteristics deteriorate. If the content of oxygen (O) in the second composite material exceeds the above range, the charge / discharge cycle of the lithium secondary battery may deteriorate.
[0252] On the other hand, according to one embodiment, the second composite material may include a second carbon layer on the surface of the silicon composite oxide, and the second carbon (C) may be contained in the second carbon layer.
[0253] Because the second composite material contains the second carbon, it can provide excellent electrical conductivity even after the electrode expands during charging and discharging, thereby further improving the performance of the lithium secondary battery.
[0254] Furthermore, according to one embodiment, the second composite material can include a silicon composite oxide and a second carbon layer on its surface, and the second silicon particles and magnesium silicate can be present in the silicon composite oxide. The second carbon can be included in at least one selected from the group consisting of the second carbon layer, the surface of the second silicon particles, and the surface of the second magnesium silicate. Furthermore, the second carbon can be present on the surface of the second silicon oxide.
[0255] Specifically, the second carbon can be included in the second carbon layer. Furthermore, the second carbon can be included by forming a second carbon layer on at least a portion of the surface of one or more selected from the group consisting of the second silicon particles, the second magnesium silicate, and the second silicon oxide.
[0256] More specifically, the second carbon can be contained in a second carbon layer formed on the surface of the silicon oxide. Furthermore, the second carbon can be contained in a second carbon layer formed on at least a portion of the surface of the second silicon particles, the surface of the second silicon oxide, and the surface of the second magnesium silicate.
[0257] Since the second carbon is contained in the second carbon layer, the mechanical properties can be enhanced, excellent electrical conductivity can be ensured even if the electrode expands during charging and discharging, and side reactions with the electrolyte are suppressed, so that the charge and discharge capacity, initial charge and discharge efficiency, and capacity retention rate of the lithium secondary battery can be improved.
[0258] Furthermore, since the thickness and carbon amount of the second carbon layer can be controlled, not only can deterioration of the life characteristics be prevented but also appropriate electrical conductivity can be obtained, thereby realizing a high-capacity negative electrode active material.
[0259] Furthermore, the carbon (C) content in the second carbon composite material may be relatively lower than the carbon (C) content in the first composite material.
[0260] The carbon (C) content in the second composite material may be 3 wt% to 15 wt%, preferably 3 wt% to 10 wt%, more preferably 3 wt% to 8 wt%, and most preferably 5 wt% to 8 wt%, based on the total weight of the second composite material.
[0261] If the content of carbon (C) in the second composite material is less than the above range, the thickness of the second carbon layer is too thin, so that the desired effect of suppressing electrical conductivity and volume expansion may be insufficient, and irreversible reactions may occur, resulting in a problem of a significant decrease in discharge capacity. Also, if the content of carbon (C) in the second composite material exceeds the above range, the thickness of the second carbon layer is too thick, so that lithium ions are difficult to release. In such a case, the initial efficiency and discharge capacity of the lithium secondary battery may decrease.
[0262] The thickness of the second carbon layer may be 10 nm to 150 nm, preferably 20 nm to 100 nm, more preferably 20 nm to 80 nm. When the thickness of the second carbon layer satisfies the above range, it can effectively prevent or reduce the pulverization of the second composite material, and effectively prevent the side reaction between the second silicon particles and the electrolyte, thereby further improving the performance of the lithium secondary battery.
[0263] When the thickness of the second carbon layer is equal to or greater than the lower limit of the above range, an improvement in electrical conductivity can be achieved, and when the thickness is within this range but equal to or less than the upper limit of the above range, a decrease in capacity of the lithium secondary battery can be suppressed.
[0264] The method for measuring the average thickness of the second carbon layer is as described above.
[0265] The second carbon layer may include at least one selected from the group consisting of amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers. Specifically, the second carbon layer may include at least one selected from the group consisting of amorphous carbon and crystalline carbon. The type of the second carbon layer is as described for the first carbon layer.
[0266] The second carbon layer can include one or more carbon layers.
[0267] When the second composite material includes one or more layers of the second carbon layer, each carbon layer can be formed thin and uniform along the entire outer shape of the carbon layer while maintaining the outer shape of the carbon layer. A part or most of the second carbon layer can surround the entire surface of the silicon composite oxide. In such a case, when the second carbon layer is formed thin and uniform on the surface of the silicon composite oxide, the electrical contact between the particles contained in the second composite material or the negative electrode active material can be improved.
[0268] Specifically, when the second carbon layer of the second composite material includes two or more layers, it can include a 2-1 carbon layer and a 2-2 carbon layer.
[0269] The types of the 2-1 carbon layer and the 2-2 carbon layer are as described above. Here, the types of the 2-1 carbon layer and the 2-2 carbon layer may be different from each other.
[0270] The second composite material has an average particle size (D 50 ).
[0271] Average particle diameter (D 50 If D is less than the above range, when the negative electrode slurry (negative electrode active material composition) is prepared using the second composite material, the particles of the second composite material may aggregate and the dispersibility may decrease. 50If the specific surface area exceeds the above range, the composite material particles will expand significantly due to charging of lithium ions, and the bonding ability between the composite material particles and between the composite material particles and the current collector will decrease as charging and discharging are repeated, resulting in a significant decrease in life characteristics and a decrease in activity due to a decrease in the specific surface area.
[0272] Furthermore, according to one embodiment, the second composite material may have a composite structure in which the second silicon particles, the second silicon oxide, and the magnesium silicate are simultaneously contained and these components are uniformly dispersed. Also, each component contained in the second composite material and its particle size can be adjusted to a specific range. If the size of each of the second silicon particles, the second silicon oxide, and the magnesium silicate is too large, there may be a problem that the second composite material cannot fully exhibit the desired function.
[0273] On the other hand, the second composite material is 3m 2 / g~20m 2 / g, preferably 3m 2 / g~15m 2 / g, more preferably 3m 2 / g~10m 2 / g specific surface area (Brunauer-Emmett-Teller method; BET). If the specific surface area of the second composite material is less than the above range, the output characteristics of the lithium secondary battery may be reduced. If it exceeds the above range, it becomes difficult to prepare a negative electrode active material slurry suitable for application to the negative electrode current collector of the lithium secondary battery, and the contact area with the electrolyte increases, which may promote the decomposition reaction of the electrolyte or cause a side reaction in the lithium secondary battery.
[0274] The second composite material had a density of 1.8 g / cm 3 ~2.5g / cm 3 , preferably 2.0 g / cm 3 ~2.5g / cm 3 , more preferably 2.0 g / cm 3 ~2.4g / cm 3The density may vary depending on the amount of coverage of the second carbon layer. In that case, the density may refer to the true density. The measurement method is as described above.
[0275] When the density of the second composite material satisfies the above range, the impregnation of the electrolyte is improved, and thus the initial charge / discharge capacity and life characteristics of the lithium secondary battery can be further improved.
[0276] On the other hand, according to one embodiment, the second composite material may include a silicate containing other metals in addition to magnesium. The other metals may be at least one selected from the group consisting of alkali metals, alkaline earth metals, elements of Groups 13 to 16, transition metals, rare earth elements, and combinations thereof. Specific examples thereof include Li, Ca, Sr, Ba, Y, Ti, Zr, Hf, V, Nb, Cr, Mo, W, Fe, Pb, Ru, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, and Se.
[0277] A lithium secondary battery using the second composite material in the negative electrode can further improve its discharge capacity, initial efficiency, and capacity retention rate.
[0278] According to one embodiment, silicon-carbon mixtures, specifically silicon-carbon mixtures (1) and (2) having desired physical properties, can be obtained by appropriately selecting and adjusting at least one of the first composite materials (1) and (2) as the first composite material and the second composite material, respectively.
[0279] For example, a silicon-carbon mixture can include a first composite material (1) and a second composite material.
[0280] Alternatively, the silicon-carbon mixture may include a first composite material (2) and a second composite material.
[0281] Alternatively, the silicon-carbon mixture may include a first composite material (1), a first composite material (2), and a second composite material. [Method of preparing silicon-carbon mixture]
[0282] In one embodiment, a method for preparing a silicon-carbon mixture includes a first step of obtaining a first composite material; a second step of obtaining a second composite material; and a third step of mixing the first composite material and the second composite material, where the first composite material includes first silicon particles and a first carbon, and the second composite material includes second silicon particles, magnesium silicate, and a second carbon.
[0283] According to this method for preparing silicon-carbon mixture, the etching conditions and carbon coating conditions can be adjusted in various ways, and thus the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture, as well as physical properties such as specific surface area, density, and porosity, can be adjusted and optimized in various ways. Therefore, the performance and reliability of lithium secondary batteries can be further improved.
[0284] Furthermore, this preparation method has the advantage that it allows for large scale production in a continuous manner with minimal steps. A first step of obtaining a first composite material
[0285] First, the method for preparing a silicon-carbon mixture includes a first step of obtaining a first composite material containing first silicon particles and a first carbon.
[0286] The first step of obtaining the first composite material can include a step 1-1 of etching a first silicon-based raw material powder using an etching solution containing a fluorine (F) atom-containing compound, a step 1-2 of filtering and drying the product obtained by etching to obtain a silicon composite material, and a step 1-3 of forming a first carbon inside the silicon composite material using a chemical pyrolysis deposition method and forming a first carbon layer on the surface of the silicon composite material to obtain the first composite material.
[0287] Step 1-1 can include etching the first silicon-based raw material powder with an etching solution containing a fluorine (F) atom-containing compound.
[0288] The first silicon-based raw material powder can include a powder containing silicon capable of reacting with lithium, for example, a powder containing at least one of silicon, silicon oxide, and silicon dioxide.
[0289] Specifically, the first silicon-based raw material powder can include at least two selected from silicon, silicon oxide, and silicon dioxide. Specifically, the first silicon-based raw material powder can include at least two selected from silicon, silicon oxide, and silicon dioxide. x It may contain a lower silicon oxide powder represented by (0.9≦x<1.2).
[0290] The first silicon-based raw material powder is amorphous or crystalline SiO prepared by a gas phase method. x (Size of silicon crystals: about 2 nm to 3 nm) The average particle size as the median size of the first silicon-based raw material powder may be about 0.5 μm to 30 μm, preferably about 0.5 μm to 25 μm, and more preferably about 0.5 μm to 10 μm.
[0291] If the average particle size of the first silicon-based raw material powder is less than the above range, the volume density may be too small, resulting in a decrease in the charge / discharge capacity per unit volume. If the average particle size of the first silicon-based raw material powder is more than the above range, it may be difficult to prepare an electrode, or the powder may peel off from the current collector. The average particle size is determined by measuring the particle size distribution by a laser light diffraction method, using a ratio of D 50 (i.e., the particle size when the cumulative weight is 50%).
[0292] Furthermore, this method can further include forming a carbon layer on a surface of the first silicon-based raw material powder by using a chemical pyrolysis deposition method. Therefore, the first silicon-based raw material powder on which the carbon layer is formed can be used as the silicon-based raw material powder.
[0293] Specifically, the etching step of step 1-1 can be carried out immediately after the carbon layer is formed on the surface of the first silicon-based raw material powder containing silicon particles. In such a case, there is an advantage that uniform etching is possible and a high yield can be obtained.
[0294] The step of forming the carbon layer can be carried out by a method similar to or the same as the step of forming the first carbon layer in step 1-3 of the first composite material preparation method described below.
[0295] The etching process can include dry etching and wet etching.
[0296] If a dry etch is used, selective etching may be possible.
[0297] The silicon oxide of the first silicon-based raw material powder is dissolved and eluted during the etching process to form pores.
[0298] Further, the pores can be considered to be formed, for example, by the following reaction schemes 2 and 3. [Reaction Scheme 2] [ka] [Reaction Scheme 3] [ka]
[0299] Silicon dioxide is converted to SiF by the reaction mechanism shown in the above reaction scheme. 4 and H 2 SiF 6 Pores (voids) can be formed that are dissolved away in the form of
[0300] Also, depending on the extent of etching, silicon oxide, for example silicon dioxide, contained in the first composite material may be removed and pores may be formed therein.
[0301] The extent of pore formation may vary depending on the extent of etching.
[0302] In addition, the O / Si ratio during etching and the specific surface area of the silicon composite can change significantly, and the specific surface area and density of the silicon composite in which pores are formed can change significantly before and after carbon coating.
[0303] By etching, it is possible to obtain a silicon composite powder in which a plurality of pores are formed on the surface of the silicon composite particle, or on the surface and inside the particle.
[0304] Here, etching refers to a method of treating the first silicon-based raw material powder with an etching solution containing a fluorine (F) atom-containing compound.
[0305] Generally used etching solutions containing fluorine atoms can be used without limitation as the etching solution containing a fluorine (F) atom-containing compound as long as the effect of the etching solution is not impaired.
[0306] Specifically, fluorine (F) atom-containing compounds include HF, NH 4 F, and HF 2 The etching process can be carried out more quickly because a fluorine (F) atom-containing compound is used.
[0307] The etching solution may further comprise one or more acids selected from the group consisting of organic acids, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, and chromic acid.
[0308] As an etching condition, the stirring temperature (treatment temperature) may be, for example, 10°C to 90°C, preferably 10°C to 80°C, and more preferably 20°C to 70°C.
[0309] The silicon composite material resulting from the etching may include the first silicon particles.
[0310] This etching can result in a silicon composite material having a plurality of pores formed on the surface, inside, or both of the silicon composite particles, where the silicon composite material can have a three-dimensional (3D) structure in which two or more first silicon particles are bonded to each other.
[0311] Another feature of the silicon composite material is that the average grain size of the silicon composite material is hardly changed by etching.
[0312] That is, the average particle size of the first silicon-based raw material powder before etching is approximately the same as the average particle size of the silicon composite material obtained by etching. The difference (change) between the average particle size of the first silicon-based raw material powder and the average particle size of the silicon composite material can be within about 5%.
[0313] In addition, the number of oxygen atoms present on the surface of the silicon composite material can be reduced by etching. That is, the oxygen fraction on the surface of the silicon composite material can be significantly reduced by etching, and the surface resistance can be reduced. In such a case, the electrochemical properties, particularly the life properties, of the lithium secondary battery can be further improved.
[0314] Furthermore, since a large amount of silicon oxide (silicon dioxide) is removed by selective etching, the first silicon particles can contain a very high fraction of silicon (Si) on their surfaces compared to oxygen (O). In other words, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms present in the silicon composite material can be significantly reduced. In such a case, a lithium secondary battery with excellent capacity retention, discharge capacity, and initial efficiency can be obtained.
[0315] Furthermore, pores and voids may be formed in the areas where the silicon oxide (silicon dioxide) has been removed, and as a result, the specific surface area of the silicon composite material may be increased compared to the specific surface area of the first silicon-based raw material powder before etching.
[0316] According to one embodiment, physical properties such as element content and specific surface area may change before and after the etching step, that is, the element content, specific surface area, and other physical properties of the first silicon-based raw material powder before the etching step and the silicon composite material after the etching step may differ from each other.
[0317] Here, the silicon composite material after the etching step and before the carbon coating and the second silicon composite material have a porous structure unless otherwise specified.
[0318] The internal porosity of the silicon composite material after the etching step is 10% to 50%, preferably 15% to 50%, and more preferably 20% to 50%.
[0319] When the internal porosity of the silicon composite material satisfies the above range, it can be more advantageous in obtaining the desired effects.
[0320] , In the first method for preparing a silicon composite material, the first-2 step can include filtering and drying the product obtained by etching to obtain a silicon composite material. The filtering and drying steps can be carried out by a commonly used method.
[0321] In the method for preparing the first composite material, step 1-3 can include forming a first carbon inside a silicon composite material using a chemical pyrolysis deposition method, and forming a first carbon layer on the surface of the silicon composite material to prepare the first composite material.
[0322] The first carbon layer may include at least one selected from the group consisting of amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers.
[0323] The step of forming a first carbon inside the silicon composite material and forming a first carbon layer on the surface of the silicon composite material can be carried out by injecting at least one carbon source gas selected from the compounds represented by the following formulas 1 to 3, and reacting the silicon composite material obtained in step 1-2 in a gaseous state at 400°C to 1200°C.
[0324] [Formula 1] [ka] (In formula 1, N is an integer of 1 to 20, and A is 0 or 1.) [Formula 2] [ka] (In formula 2, N is an integer of 2 to 6, and B is an integer of 0 to 2.) [Formula 3] [ka] (In formula 3, x is an integer from 1 to 20, y is an integer from 0 to 25, and z is an integer from 0 to 5.)
[0325] The compound represented by formula 1 may be at least one selected from the group consisting of methane, ethane, propane, butane, methanol, ethanol, propanol, propanediol, and butanediol. The compound represented by formula 2 may be at least one selected from the group consisting of ethylene, acetylene, propylene, butylene, butadiene, and cyclopentene. The compound represented by formula 3 may be at least one selected from the group consisting of benzene, toluene, xylene, ethylbenzene, naphthalene, anthracene, and dibutylhydroxytoluene (BHT).
[0326] The carbon source gas may further comprise at least one inert gas selected from hydrogen, nitrogen, helium, and argon.
[0327] The reaction can be carried out at, for example, 400°C to 1,200°C, specifically 500°C to 1,100°C, and more specifically 600°C to 1,000°C.
[0328] The reaction time (or heat treatment time) can be appropriately adjusted according to the heat treatment temperature, the pressure during the heat treatment, the composition of the gas mixture, and the desired carbon coating amount. For example, the reaction time may be, but is not limited to, 10 minutes to 100 hours, specifically 30 minutes to 90 hours, and more specifically 50 minutes to 40 hours.
[0329] According to the method for preparing the first composite material of one embodiment, a thin and uniform first carbon layer can be formed on the surface of the silicon composite material by a gas-phase reaction of a carbon source gas even at a relatively low temperature. Moreover, the exfoliation reaction in the first carbon layer thus formed does not substantially occur.
[0330] In addition, the first carbon layer is formed uniformly over the entire surface of the silicon composite material by a gas-phase reaction using chemical pyrolysis deposition, making it possible to form a highly crystalline carbon film (carbon layer).
[0331] In addition, since the multiple pores formed by the etching in step 1-1 and / or step 1-2 can be coated (embedded) with carbon by a gas-phase reaction using a chemical pyrolysis deposition method, the porosity of the first composite material and the silicon-carbon mixture can be controlled, and the desired effect can be obtained.
[0332] Therefore, when a silicon-carbon mixture containing the first composite material is used as a negative electrode active material, the electrical conductivity of the negative electrode active material can be improved without changing the structure.
[0333] According to one embodiment, when a reactive gas containing a carbon source gas and an inert gas is supplied to a silicon composite material, the reactive gas can penetrate into the pores of the silicon composite material, so that the first carbon is sufficiently formed (coated or embedded) inside the silicon composite material, and a first carbon layer is formed on the surface of the silicon composite material. As a result, the electrical conductivity of the negative electrode active material can be improved.
[0334] The specific surface area of the first composite material may decrease relative to the amount of carbon coating.
[0335] Furthermore, by adjusting the etching conditions and / or carbon coating conditions, the porosity of the first composite material and also the porosity of the silicon-carbon mixture can be controlled as desired. That is, because carbon penetrates the silicon composite material and fills the pores, and because a carbon layer is formed on the surface of the silicon composite material, a first composite material with controlled porosity, specifically, first composite material (1) and first composite material (2), can be obtained. This method allows the porosity of the silicon-carbon mixture to be optimized according to the properties required for the lithium secondary battery.
[0336] The structure of the graphene-containing material may be of layer, nanosheet type, or a mixed structure of several flakes.
[0337] When the first carbon layer containing the graphene-containing material is uniformly formed over the entire surface of the silicon composite material, the graphene-containing material with improved electrical conductivity and flexibility against volume expansion can be directly grown on the surface of the first silicon particles, suppressing volume expansion. Furthermore, the coating of the first carbon layer reduces the possibility of direct contact of silicon with the electrolyte, suppressing the formation of a solid electrolyte interphase (SEI) layer.
[0338] Meanwhile, after many of the pores formed after etching are covered with carbon, the first carbon may be inserted into the surface and internal pores of the first composite material.
[0339] The porosity of the first composite material after carbon coating is as described above.
[0340] Furthermore, according to one embodiment, after step 1-3 (in step 1-3, the first carbon is formed inside the silicon composite material, and the first carbon layer is formed on the surface of the silicon composite material), one or more first composite materials can be bonded to each other to form an aggregate. The method can further include crushing and classifying the first composite material so that the average particle size of the first composite material is 2 μm to 15 μm. Classification can be performed to adjust the particle size distribution of the first composite material, and dry classification, wet classification, or classification using a sieve can be used. In dry classification, the steps of dispersion, separation, recovery (separation of solid and gas), and discharge are performed sequentially or simultaneously using an air flow, and in this case, in order to prevent the classification efficiency from being reduced due to interference between particles, particle shape, air flow turbulence, velocity distribution, static electricity, etc., pretreatment (adjustment of moisture, dispersibility, humidity, etc.) can be performed before classification to adjust the moisture or oxygen concentration in the air flow used. Furthermore, the desired particle size distribution can be obtained by performing the grinding and classification of the first composite material at the same time. After grinding, it is effective to separate the coarse powder fraction and the granular fraction with a classifier or sieve. A second step of obtaining a second composite material
[0341] In one embodiment, the method for preparing the silicon-carbon mixture includes a second step of obtaining a second composite material comprising second silicon particles, magnesium silicate, and second carbon.
[0342] The step of obtaining the second composite material includes a step 2-1 of obtaining a silicon composite oxide using a second silicon-based raw material and a magnesium-based raw material; a step 2-2 of obtaining a silicon composite oxide powder by pulverizing and / or classifying the silicon composite oxide; and a step 2-3 of forming a second carbon layer on the surface of the silicon composite oxide powder by a chemical pyrolysis deposition method to obtain the second composite material.
[0343] The second method for preparing the composite material has the advantage that it allows for mass production by a continuous method with a minimum of steps.
[0344] Specifically, in the second method for preparing a composite material, step 2-1 may include obtaining a silicon composite oxide using a silicon-based raw material and a magnesium-based raw material. Step 2-1 may be carried out, for example, using the method described in Korean Patent Publication No. 2018-0106485.
[0345] Additionally, the second silicon-based raw material may be the same as or similar to the first silicon-based raw material.
[0346] The silicon composite oxide may include magnesium silicate.
[0347] Specifically, the second silicon-based raw material and the magnesium-based raw material are heated at different temperatures to vaporize, and then the vapor is evaporated and cooled to obtain a silicon composite oxide.
[0348] The second silicon-based raw material powder can contain at least one selected from silicon, silicon oxide, and silicon dioxide.
[0349] The magnesium-based raw material may include metallic magnesium.
[0350] On the other hand, the average particle size of the second silicon-based raw material is not particularly limited. For example, the average particle size of the silicon powder may be 5 μm to 50 μm, 10 μm to 40 μm, or 15 μm to 30 μm, and the average particle size of the silicon dioxide powder may be 5 nm to 50 nm, 10 nm to 40 nm, or 15 nm to 30 nm.
[0351] When the second silicon-based raw material having an average particle size within the above range is used, the deposition and evaporation of silicon dioxide becomes uniform, thereby making it possible to obtain fine second silicon particles.
[0352] The second silicon-based raw material and the magnesium-based raw material are placed in crucibles in a vacuum reactor, respectively, and are heated and evaporated at different temperatures. This is then evaporated and cooled to obtain a silicon composite oxide.
[0353] The heating and evaporation of the second silicon-based raw material can be carried out at a pressure of 0.0001 Torr to 2 Torr at 900°C to 1,800°C, preferably 1,000°C to 1,600°C, and more preferably 1,200°C to 1,600°C. If the temperature is lower than the above range, the reaction may not proceed smoothly, which may result in a decrease in productivity. If the temperature exceeds the above range, the reactivity may decrease.
[0354] The heating and evaporation of the magnesium-based raw material can be carried out at a pressure of 0.0001 Torr to 2 Torr and at a temperature of 500°C to 1,100°C, 600°C to 1,000°C, or 650°C to 900°C.
[0355] When the heating and evaporation of the second silicon-based raw material and the magnesium-based raw material satisfy the above ranges, fine second silicon particles and fine magnesium silicate particles can be produced, thereby obtaining the desired SiO x It is possible to obtain silicon oxide (silicon oxide compound) having a composition (0.4≦x≦2).
[0356] On the other hand, the deposition can be carried out at a temperature of 300°C to 800°C, preferably 400°C to 700°C.
[0357] Cooling can be performed by rapidly cooling to room temperature using water cooling. In addition, cooling can be performed at room temperature while injecting an inert gas. Inert gases include carbon dioxide gas, argon (Ar), helium (He), and nitrogen (N 2 ) and hydrogen (H 2 ) may be at least one selected from the following.
[0358] The second silicon-based raw material and the magnesium-based raw material are heated and evaporated, then deposited on the substrate in the reactor, and a silicon composite oxide is synthesized by a uniform gas-phase reaction of the particles. This prevents the rapid growth of the second silicon due to an exothermic reaction caused by localized excessive mixing of magnesium, as occurs in solid-phase reactions.
[0359] On the other hand, the method may further include heat treatment of the silicon composite oxide.
[0360] The heat treatment can be carried out at 700° C. to 950° C. Specifically, the heat treatment can be carried out at 800° C. to 950° C., preferably 900° C. to 930° C., for 1 to 10 hours or 1 to 5 hours.
[0361] Step 2-2 in one embodiment can further include pulverizing and / or classifying the silicon composite oxide obtained in step 2-1 so that the silicon composite oxide has an average particle size of 3 μm to 15 μm.
[0362] More specifically, the silicon composite oxide obtained in the step 2-1 may be pulverized, and the pulverization may be performed to obtain an average particle size (D 50 ) may be 3 μm to 10 μm, specifically 3 μm to 8 μm.
[0363] For the grinding, grinding equipment known in the art can be used, for example, grinding can be performed using at least one selected from the group consisting of a jet mill, a ball mill, a stirred media mill, a roll mill, a hammer mill, a pin mill, a disk mill, a colloid mill, and an atomizer mill.
[0364] Specifically, the grinding can be performed using a ball mill, which moves grinding media such as balls or beads and grinds the material to be ground using impact force, friction force, or compression force supplied by kinetic energy, or a stirring media mill, or a roll mill, which grinds the material using compression force from rollers. Furthermore, a jet mill can be used, which causes the material to be ground to collide with an interior material or with other materials at high speed and grinds the material using the impact force supplied by the collision. Furthermore, a hammer mill, a pin mill, or a disk mill can also be used. In addition, a colloid mill or an atomizer mill that uses shear force can be used as a high-pressure wet opposed collision type disperser.
[0365] Furthermore, classification may be performed using at least one method selected from dry classification, wet classification, and sieve classification.
[0366] According to one embodiment, a dry classifier equipped with a cyclone can be used in conjunction with a jet mill.
[0367] In a jet mill, the processes of dispersion, separation (separation of fine particles from coarse particles), recovery (separation of solids from gas), and discharge can be carried out sequentially using airflow. In such cases, the classification efficiency must not be impaired by the effects of particle interference, particle shape, airflow turbulence, velocity distribution, and static electricity.
[0368] That is, the air stream may be pretreated (to adjust moisture, dispersibility, humidity, etc.) prior to classification to adjust moisture and oxygen concentrations.
[0369] Furthermore, by performing pulverization and classification at the same time, a desired particle size distribution can be obtained.
[0370] In the method for preparing the second composite material, the 2-3rd step can include forming a second carbon layer on the surface of the silicon composite oxide powder by using a chemical pyrolysis deposition method to obtain the second composite material.
[0371] The second carbon layer may be formed on the surface of the silicon composite oxide powder, as well as on the surface of at least one particle selected from the group consisting of second silicon particles, magnesium silicate (particles), and second silicon oxide (particles) constituting the silicon composite oxide powder.
[0372] The second carbon layer can include at least one selected from the group consisting of amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers.
[0373] The step of forming the second carbon layer can be carried out in the same manner as steps 1-3.
[0374] According to one embodiment, the method may further include crushing and classifying the second composite material after the step 2-3 (after the formation of the second carbon layer in the step 2-3) so that the second composite material has a desired average particle size. The crushing and classifying steps are as described above. The third step
[0375] The step of preparing a silicon-carbon mixture includes a third step of mixing the first composite material with the second composite material.
[0376] The mixing weight ratio of the first composite material to the second composite material may be 90:10 to 5:95, 90:10 to 10:90, 90:10 to 20:80, 90:10 to 60:40, 90:10 to 65:35, or 90:10 to 70:30. When the mixing weight ratio of the first composite material to the second composite material satisfies the above range, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture can be optimized. As a result, a silicon-carbon mixture having desired properties can be obtained.
[0377] If the mixing weight ratio of the first composite material to the second composite material is outside the above range, it may be difficult to obtain the desired effects, and in particular the cycle characteristics of the lithium secondary battery may deteriorate.
[0378] The mixing can be carried out by at least one method selected from dry mixing and wet mixing.
[0379] According to one embodiment, the mixing can be performed, for example, using a co-rotating mixer to prepare a powder containing mixed phase particles. The rotation speed during mixing can be 1,000 to 3,000 rpm, for example, about 2,000 rpm, and the mixing time can be 2 to 20 minutes, preferably 3 to 10 minutes, more preferably 5 to 8 minutes, for example, about 6 minutes. When the mixing speed and mixing time are within the above ranges, the first composite material and the second composite material can be efficiently and uniformly mixed.
[0380] Meanwhile, according to one embodiment, the silicon-carbon mixture can be prepared by a preparation method including the steps of: mixing the silicon composite material obtained in step 1-2 with the silicon composite oxide powder obtained in step 2-2 to prepare a silicon composite material mixture; and forming a carbon layer on the silicon composite material mixture.
[0381] In the silicon composite material mixture, the mixing weight ratio of the silicon composite material obtained in the 1-2 step and the silicon composite oxide powder obtained in the 2-2 step may be 90:10 to 5:95, 90:10 to 10:90, 90:10 to 20:80, 90:10 to 60:40, 90:10 to 65:35, or 90:10 to 70:30. When the mixing weight ratio of the silicon composite material mixture satisfies the above range, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture can be optimized. As a result, a silicon-carbon mixture having desired properties can be obtained.
[0382] Furthermore, the step of forming a carbon layer on the silicon composite mixture can be carried out in the same manner as or similar to the steps 1-3. This method can further include a step of grinding the powder obtained after forming the carbon layer (grinding step). The grinding step is as described above. negative electrode active material
[0383] In one embodiment, the negative electrode active material may include the silicon-carbon mixture described above.
[0384] In addition, the negative electrode active material may further include a carbon-based negative electrode active material, specifically, a graphite-based negative electrode active material.
[0385] When the negative electrode active material is a mixture of a silicon-carbon mixture and a carbon-based negative electrode active material, such as a graphite-based negative electrode active material, the electrical resistance of the negative electrode active material can be reduced and the expansion stress caused by charging can be alleviated at the same time. The carbon-based negative electrode material can include at least one selected from the group consisting of natural graphite, synthetic graphite, soft carbon, hard carbon, mesocarbon, carbon fiber, carbon nanotube, pyrolytic carbon, coke, glass carbon fiber, sintered organic polymer compound, and carbon black.
[0386] The content of the carbon-based negative electrode material may be 5% to 70% by weight, preferably 10% to 60% by weight, and more preferably 10% to 50% by weight, based on the total weight of the negative electrode active material.
[0387] In addition, when silicon particles with a crystallite size of 20 nm or less, for example 15 nm or less, are mixed with graphite-based materials, which generally have a small volume expansion, the silicon particles alone do not cause a large volume expansion, and therefore a lithium secondary battery with excellent cycle characteristics can be obtained. Lithium secondary battery
[0388] According to one embodiment, a negative electrode including a negative electrode active material and a lithium secondary battery including the same are provided.
[0389] The lithium secondary battery may include a positive electrode, a negative electrode, a separator inserted between the positive electrode and the negative electrode, and a non-aqueous liquid electrolyte having a lithium salt dissolved therein. The negative electrode active material may include a silicon-carbon mixture.
[0390] The negative electrode may be composed of only the negative electrode mixture, or may be composed of a negative electrode current collector and a negative electrode mixture layer (negative electrode active material layer) supported thereon. Similarly, the positive electrode may be composed of only the positive electrode mixture, or may be composed of a positive electrode current collector and a positive electrode mixture layer (positive electrode active material layer) supported thereon. Furthermore, the negative electrode mixture and the positive electrode mixture may each further include a conductive agent and a binder (binding agent).
[0391] The materials constituting the negative electrode current collector and the positive electrode current collector may be made of materials known in the art. The binder and conductive material added to the negative electrode and positive electrode may be made of materials known in the art.
[0392] When the negative electrode is composed of a current collector and an active material layer supported thereon, the negative electrode can be prepared by applying a negative electrode active material composition containing a silicon-carbon mixture to the surface of the current collector and drying it.
[0393] Furthermore, the lithium secondary battery includes a non-aqueous liquid electrolyte containing a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, a solvent commonly used in the field can be used as the non-aqueous solvent. Specifically, an aprotic organic solvent can be used. Examples of the aprotic organic solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, cyclic carboxylic acid esters such as furanone, chain carbonates such as diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate, chain ethers such as 1,2-methoxyethane, 1,2-ethoxyethane, and ethoxymethoxyethane, and cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran. These can be used alone or in combination of two or more.
[0394] The lithium secondary battery can include a non-aqueous lithium secondary battery.
[0395] The negative electrode active material and the lithium secondary battery using the silicon-carbon mixture of one embodiment can improve not only the initial charge-discharge efficiency and the capacity retention rate but also the charge-discharge capacity. EXAMPLES
[0396] The present invention will be described in detail below with reference to examples. The following examples are merely illustrative of the present invention, and the scope of the present invention is not limited thereto. <Preparation of the first composite material> Preparation Example 3-1
[0397] (1) Step 1-1: Silicon oxide (SiO ) is a silicon oxide (oxygen-containing silicon compound) (Preparation Example 1-1) having the physical properties shown in Table 1 below, prepared by a vapor deposition method using silicon powder and silicon dioxide powder. x , x=0.9) powder (50 g) was dispersed in water. While stirring at a speed of 300 rpm, 50 mL of 40 wt % HF aqueous solution was added as an etching solution, and the silicon-based raw material (first silicon-based raw material) powder was etched for 1 hour. (2) Step 1-2: The product obtained by the above etching was filtered and dried at 150 ° C for 2 hours to prepare a dry composite material. Next, in order to control the particle size of the composite material, it was crushed using a mortar to an average particle size of 4.5 μm, and a porous silicon composite material (Preparation Example 2-1) having the contents and physical properties of each component shown in Table 2 below was prepared.
[0398] (3) Step 1-3: 10 g of the porous silicon composite material was placed in a tubular electric furnace, and argon (Ar) and methane gas were each passed through at a rate of 1 L / min. After maintaining at 900°C for 1 hour, the material was cooled to room temperature to form a first carbon inside the silicon composite material and a first carbon layer on the surface of the silicon composite material, thereby preparing a first silicon-carbon composite material having the contents and physical properties of each component shown in Table 3 below.
[0399] (4) Step 1-4: In order to control the particle size of the first silicon-carbon composite material, the first silicon-carbon composite material was pulverized by a mechanical method and classified to have an average particle size of 5.0 μm, thereby preparing a first composite material having the contents and physical properties of each component shown in Table 3 below. Preparation Examples 3-2 to 3-7
[0400] First composite materials (Preparation Examples 3-2 to 3-7) having the contents and physical properties of each component shown in Table 3 below were prepared in the same manner as Preparation Example 3-1, except that the contents and physical properties of each component were adjusted using porous silicon composite materials (Preparation Examples 2-2 to 2-5) having the contents and physical properties of each component shown in Table 2 below. Preparation Examples 3-8 to 3-10
[0401] Using the porous silicon composite material (Preparation Examples 2-2 to 2-5) having the content and physical properties of each component shown in Table 2 below, the content and physical properties of each component were adjusted, 10 g of the porous silicon composite material was placed in a tubular electric furnace, argon (Ar) gas and ethylene gas were each flowed at a rate of 0.5 L / min, and this was maintained at 750°C for 2 hours, and then cooled to room temperature to form a first carbon layer inside the silicon composite material and a first carbon layer on the surface of the silicon composite material. The first composite materials (Preparation Examples 3-8 to 3-10) having the content and physical properties of each component shown in Table 3 below were prepared in the same manner as in Preparation Example 3-1, except that. <Preparation of the second composite material> Preparation Example 4-1
[0402] (1) Step 2-1: 8 kg of silicon powder having an average particle size of 20 μm and 16 kg of silicon dioxide powder having an average particle size of 20 nm were added to 50 kg of water, and the mixture was stirred for 12 hours to mix uniformly. The mixture was then dried at 200° C. for 24 hours to obtain a raw powder mixture.
[0403] The raw material powder mixture and 2 kg of metallic magnesium were placed in crucible A and crucible B of a vacuum reactor, respectively. After the pressure was reduced to 0.1 Torr, the temperature of crucible A was raised to 1,500°C and the temperature of crucible B to 900°C, and the reaction was carried out for 5 hours.
[0404] The silicon composite oxide mass deposited on the substrate in the reactor by a high-temperature gas phase reaction was rapidly cooled to room temperature by a water-cooled substrate.
[0405] (2) Step 2-2: A lump of silicon composite oxide was pulverized by a mechanical method, and the particle size was controlled to obtain a silicon composite oxide powder having an average particle size of 6 μm.
[0406] (3) Step 2-3: 50 g of silicon composite oxide powder was placed in a tubular electric furnace, and argon (Ar) and methane gas were introduced at a rate of 1 L / min each. The furnace was maintained at 900°C for 1 hour to prepare a second composite material (Preparation Example 4-1) having the contents and physical properties of each component shown in Table 4 below. Preparation Example 4-2
[0407] A second composite material (Preparation Example 4-2) was prepared in the same manner as in Preparation Example 4-1, except that the contents of each component and the physical properties of the composite material were adjusted as shown in Table 4 below. Example 1 Preparation of silicon-carbon mixtures
[0408] The first composite material of Preparation Example 3-1 and the second composite material of Preparation Example 4-1 were mixed in a weight ratio of 90:10. Here, mixing was performed using a co-rotating mixer (THINKY MIXER) to prepare a powder containing mixed phase particles composed of the first composite material and the second composite material. Mixing was performed for about 6 minutes at a rotation speed of about 2,000 rpm. The physical properties of the silicon-carbon mixture thus prepared are shown in Tables 5 and 7 below. Fabrication of lithium secondary batteries
[0409] A negative electrode and a battery (coin cell) containing this silicon-carbon mixture as the negative electrode active material were fabricated.
[0410] The negative electrode active material, Super-P as a conductive material, and polyacrylic acid were mixed with water in a weight ratio of 80:10:10 to prepare a negative electrode active material composition with a solid content of 45%.
[0411] This negative electrode active material composition was applied to a copper foil having a thickness of 18 μm and dried to prepare an electrode having a thickness of 70 μm. The copper foil to which the electrode was applied was punched out into a circle having a diameter of 14 mm to prepare a negative electrode plate for a coin cell.
[0412] Meanwhile, a 0.3 mm thick metallic lithium foil was used as the positive electrode plate.
[0413] A 25 μm thick porous polyethylene sheet was used as the separator. The electrolyte was a 1:1 volumetric mixture of ethylene carbonate (EC) and diethylene carbonate (DEC) with LiPF 6 A liquid electrolyte was used in which the electrolyte was dissolved at a concentration of 1 M. Using the above components, a coin cell with a thickness of 3.2 mm and a diameter of 20 mm was fabricated. Examples 2 to 12
[0414] A silicon-carbon mixture and a lithium secondary battery were produced in the same manner as in Example 1, except that the types of the first composite material and the second composite material, their mixing weight ratio, and O / Si molar ratio were changed as shown in Table 5 below. Comparative Example 1
[0415] As shown in Table 6 below, a lithium secondary battery was produced in the same manner as in Example 1, except that the first composite material obtained in Preparation Example 3-1 was used alone without using the second composite material. Comparative Example 2
[0416] As shown in Table 6 below, a lithium secondary battery was produced in the same manner as in Example 1, except that the second composite material obtained in Preparation Example 4-1 was used alone without using the first composite material. Comparative Example 3
[0417] As shown in Table 6 below, silicon-carbon mixtures and lithium secondary batteries were produced in the same manner as in Example 1, except that the types of the first composite material and the second composite material, their mixing weight ratio, and O / Si molar ratio were changed. <Test Example 1> X-ray diffraction analysis Measurement of the size of Si crystals
[0418] The size of the Si crystallites in the first silicon particles and the second silicon particles in the silicon-carbon mixture was calculated by the Scherrer equation in Equation 3 below, based on the full width at half maximum (FWHM) of the peak corresponding to Si(220) near 2θ=47.5° in the X-ray diffraction analysis. [Equation 3] [ka]
[0419] In Equation 3, K is 0.9, λ is 0.154 nm, B is the full width at half maximum (FWHM), and θ is the peak position (angle). The crystal structure of silicon-carbon mixtures
[0420] The crystal structure of the silicon-carbon mixture prepared in the examples was analyzed using an X-ray diffraction analyzer (Malvern Panalytical's X'Pert3). Specifically, the applied voltage was 40 kV and the applied current was 40 mA. The 2θ range was 10° to 80°, and the measurements were performed by scanning at 0.05° intervals.
[0421] As a result of the analysis, it was confirmed that the silicon-carbon mixtures of the examples each had a peak corresponding to Si crystals, indicating that they contained crystalline Si, and MgSiO 3 and SiO 2 A peak was also observed.
[0422] Specifically, as can be seen from the X-ray diffraction pattern in Figure 1, the silicon-carbon mixture of Example 1 has peaks corresponding to Si crystals at diffraction angles (2θ) of around 28.6°, 47.5°, 56.2°, 69.3°, and 76.6°, indicating that it contains crystalline Si. 3 The diffraction angles (2θ) of SiO were observed at 30.4° and 35.6°. 2 was observed at 21.3°.
[0423] As can be seen from the X-ray diffraction pattern in Figure 2, the silicon-carbon mixture of Example 7 has peaks corresponding to Si crystals at diffraction angles (2θ) of around 28.5°, 47.3°, 56.2°, 69.2°, and 76.7°, indicating that it contains crystalline Si. 3 The diffraction angles (2θ) of SiO were observed at 31.0° and 35.4°. 2 was observed at 21.3°. <Test Example 2> Electron microscope analysis
[0424] Using an ion beam scanning electron microscope (FIB-SEM, Focused Ion Beam System / Quanta 3D FEG), the porous silicon composite material prepared in Preparation Example 2-1 was observed at magnifications of 10,000x, 30,000x, and 100,000x. The results are shown in Figures 3 to 5.
[0425] Furthermore, the first composite material prepared in Preparation Example 3-1 was observed at a magnification of 10,000 times using a scanning electron microscope (FE-SEM, S-4700; Hitachi). The results are shown in FIG.
[0426] In FIG. 6, the bright white particles represent primary silicon (Si) particles (crystalline) and the dark areas represent carbon (C).
[0427] Furthermore, the first composite material prepared in Preparation Example 3-1 was observed with a transmission electron microscope (FE-TEM, TECNAI G2 F20). The results are shown in Figures 7 and 8.
[0428] Figure 7 is an FE-TEM photograph of the first composite material prepared in Preparation Example 3-1. The bright field image is shown. Figure 8 shows the dark field and bright field images.
[0429] As can be seen from Figures 7 and 8, a carbon coating layer having a thickness of about 27±5 nm was formed on the surface of the first composite material. <Test Example 3> Analysis of the content of component elements and density of composite material
[0430] The magnesium (Mg), oxygen (O), carbon (C), and silicon (Si) contents in the first composite, the second composite, and the silicon-carbon mixture were analyzed.
[0431] The magnesium (Mg) content was analyzed by inductively coupled plasma (ICP) analysis. The oxygen (O) and carbon (C) contents were measured by an elemental analyzer. The silicon (Si) content was calculated based on the oxygen (O) and magnesium (Mg) contents.
[0432] On the other hand, the components contained in the silicon-carbon mixture were confirmed using FIB-SEM EDS (S-4700; Hitachi, QUANTA 3D FEG; FEI, EDS system; EDAX). As a result, Mg, C, O, and Si components were observed in the silicon-carbon mixture.
[0433] On the other hand, the densities of the first composite particle, the second composite particle, and the silicon-carbon mixture were measured using an Acupick II1340 manufactured by Shimadzu Corporation after purging with helium gas 200 times in a sample holder set at a temperature of 23°C. <Test Example 4> Measurement of average particle size of composite material and composite material particles
[0434] The average particle size (D 50 ) is the average diameter D 50 , that is, the particle size or median size when the cumulative volume is 50%. <Test Example 5> Measurement of capacity, initial efficiency, and capacity retention rate of lithium secondary batteries
[0435] The monocells (lithium secondary batteries) prepared in the examples and comparative examples were charged at a constant current of 0.1 C until the voltage reached 0.005 V, and then the current reached 0.005 C at a constant voltage. Next, they were discharged at a constant current of 0.1 C until the voltage reached 2.0 V, and the charge capacity (mAh / g), discharge capacity (mAh / g), and initial efficiency (%) were measured. The results are shown in Tables 5 and 6 below. [Equation 4] Initial efficiency (%) = discharge capacity / charge capacity x 100
[0436] In addition, each of the monocells (lithium secondary batteries) prepared in the examples and comparative examples was charged at a constant current of 0.1 C until the voltage reached 4.25 V, and then the current reached 0.05 C at a constant voltage. Next, the monocells were discharged at a constant current of 0.1 C until the voltage reached 2.5 V. Under these conditions, 1,000 cycles were performed, and the capacity retention rate at 1,000 cycles was measured according to the following equation 5. [Equation 5] Capacity retention at 1,000 cycles (%) = Discharge capacity at 1,000 cycles / Discharge capacity at 1st cycle x 100
[0437] The contents and physical properties of each element in the first composite material and the second composite material prepared in the Preparation Examples are summarized in Tables 3 and 4 below, and the contents and physical properties of each element in the mixtures or composite materials prepared in the Examples and Comparative Examples, as well as the characteristics of the lithium secondary batteries using these, are summarized in Tables 5 to 7 below.
[0438] [Table 1]
[0439] [Table 2]
[0440] [Table 3]
[0441] [Table 4]
[0442] [Table 5]
[0443] [Table 6]
[0444] [Table 7]
[0445] As can be seen from Tables 5 to 7 above, in the lithium secondary batteries of Examples 1 to 12 which used silicon-carbon mixtures containing a first composite material and a second composite material as two or more composite materials, silicon particles, magnesium silicate, and carbon, and in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms satisfies a specific range, when the discharge capacity, initial efficiency, and capacity retention rate were evaluated comprehensively, all performances were improved compared to the lithium secondary batteries of Comparative Examples 1 to 3.
[0446] Specifically, the lithium secondary batteries of Examples 1 to 12, which used a silicon-carbon mixture containing a first composite material and a second composite material and having a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.09 to 0.56, almost always had a discharge capacity of about 1,400 mAh / g or more, an initial efficiency of about 83% or more, and a capacity retention rate at 50 cycles of about 85% or more. Also, the lithium secondary batteries of Examples 10 to 12 had a capacity retention rate at 1000 cycles of about 66% or more, indicating that the performance of the lithium secondary batteries was generally excellent and the reliability was improved.
[0447] In contrast, the lithium secondary battery of Comparative Example 1, which used a silicon-carbon mixture containing only the first composite material as the negative electrode active material and had a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.01, had a capacity retention of 78.4% and a capacity retention at 1000 cycles of 52%, showing a significant decrease compared to the lithium secondary batteries of the Examples.
[0448] In addition, in the lithium secondary battery of Comparative Example 2, which used a silicon-carbon mixture containing only the second composite material as the negative electrode active material and had a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.98, the discharge capacity was approximately 1,354 mAh / g, the initial efficiency was 81%, and the capacity retention rate at 1,000 cycles was 57%, which showed a significant decrease compared to the lithium secondary battery of the Example.
[0449] On the other hand, in the lithium secondary battery of Comparative Example 3 using a silicon-carbon mixture containing the first composite material and the second composite material, although the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms was 0.91, the discharge capacity was 1,368 mAh / g, the initial efficiency was 82.1%, and the capacity retention rate at 1,000 cycles was approximately 54%, showing a significant decrease compared to the lithium secondary batteries of the Examples.
[0450] On the other hand, when the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms was less than 0.06, the preparation itself was impossible.
[0451] Furthermore, according to one embodiment, the carbon content and porosity can be easily controlled, and as a result, excellent capacity retention can be maintained even after several thousand or more cycles are repeated over a long period of time while satisfying the above-mentioned molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture, thereby further improving reliability.
Claims
1. A silicon-carbon mixture comprising two or more composite materials, the silicon-carbon mixture comprising silicon particles, magnesium silicate, and carbon, the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) being 0.06 and 0.
90.
2. the two or more composite materials include a first composite material and a second composite material; the first composite material comprises first silicon particles and first carbon; 2. The silicon-carbon mixture of claim 1, wherein the second composite material comprises second silicon particles, magnesium silicate, and second carbon.
3. 3. The silicon-carbon mixture of claim 2, wherein the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in the first composite material is 0.005 to 0.50, and the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in the second composite material is 0.8 to 1.
2.
4. 3. The silicon-carbon mixture of claim 2, wherein the weight ratio of said first composite material to said second composite material is from 90:10 to 5:
95.
5. The silicon-carbon mixture includes silicon aggregates in which silicon particles are bonded to each other, and the magnesium silicate is MgSiO 3 , Mg 2 SiO 4 10. The silicon-carbon mixture of claim 1 comprising:
6. in the silicon-carbon mixture, based on the total weight of the silicon-carbon mixture: The oxygen (O) content is 1% by weight to 25% by weight, The silicon (Si) content is 35% to 80% by weight, The magnesium (Mg) content is 0.1% to 15% by weight, The carbon (C) content is 9% by weight to 50% by weight, 2. The silicon-carbon mixture of claim 1, wherein the molar ratio of magnesium (Mg) atoms to silicon (Si) atoms (Mg / Si) in the silicon-carbon mixture is 0.009 to 0.
55.
7. The silicon-carbon mixture is silicon oxide (SiO x , 0.4<x≦2).
8. The first composite material comprises a silicon composite material and a first carbon layer on a surface thereof, the first silicon particles are present in the silicon composite material, and the first carbon is contained in the first carbon layer and inside the silicon composite material; The second composite material comprises a silicon composite oxide and a second carbon layer on the surface thereof, the second silicon particles and the magnesium silicate are present in the silicon composite oxide, and the second carbon is contained in at least one selected from the group consisting of the second carbon layer, the surface of the second silicon particles, and the surface of the second magnesium silicate. The silicon-carbon mixture of claim 2.
9. The content of oxygen (O) in the first composite material is 0.1% by weight to 16% by weight based on the total weight of the first composite material; 3. The silicon-carbon mixture of claim 2, wherein the oxygen (O) content in the second composite material is 20% to 40% by weight based on the total weight of the second composite material.
10. The content of carbon (C) in the first composite material is 10% by weight to 50% by weight based on the total weight of the first composite material; 3. The silicon-carbon mixture of claim 2, wherein the carbon (C) content in the second composite material is 3% to 15% by weight based on the total weight of the second composite material.
11. A first step of obtaining a first composite material; A second step of obtaining a second composite material; and A third step of mixing the first composite material with the second composite material.
2. A method for preparing the silicon-carbon mixture of claim 1 comprising: The method of preparing the first composite material, wherein the first composite material comprises first silicon particles and a first carbon, and the second composite material comprises second silicon particles, magnesium silicate, and a second carbon.
12. The first step of obtaining the first composite material comprises: A 1-1 step of etching a first silicon-based raw material using an etching solution containing a fluorine (F) atom-containing compound; A first-2 step of obtaining a silicon composite material by filtering and drying the product obtained by the etching; and A first-3 step of forming a first carbon layer inside the silicon composite material by using a chemical pyrolysis deposition method and forming a first carbon layer on the surface of the silicon composite material to obtain a first composite material.
12. A method for preparing the silicon-carbon mixture of claim 11, comprising:
13. The second step of preparing the second composite material comprises: A step 2-1 of obtaining a silicon composite oxide using a second silicon-based raw material and a magnesium-based raw material; A step 2-2 of pulverizing and / or classifying the silicon composite oxide to obtain a silicon composite oxide powder; and A second carbon layer is formed on the surface of the silicon composite oxide powder by chemical pyrolysis deposition to obtain a second composite material.
12. A method for preparing the silicon-carbon mixture of claim 11, comprising:
14. A negative electrode active material comprising the silicon-carbon mixture of claim 1.
15. A lithium secondary battery comprising the negative electrode active material according to claim 14.
Citation Information
Patent Citations
Negative electode active material, its manufacturing method, and negative electrode and lithium battery adopting it
JP2008198610A
Negative electrode material for secondary battery, and its manufacturing method
JP2010170943A
Anode material for nonaqueous electrolyte secondary battery, its manufacturing method, and lithium ion secondary battery
JP2010267588A
Porous silicon electrode and method
JP2017520089A
Anode active material, anode containing same, and lithium secondary battery containing same
JP2019508842A